Transfer film, method for manufacturing a laminate, method for manufacturing a circuit wiring
Patent Information
- Application Number
- CN202180050844.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-25
- Filing Date
- 2021-08-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-08-17
AI Technical Summary
[0048]根据本发明,能够提供一种在将转印膜贴合于被转印体时,不易产生褶皱的转印膜。并且,根据本发明,还能够提供一种使用转印膜的层叠体的制造方法及电路配线的制造方法。
Smart Images

Figure CN115943347B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing a transfer film, a laminate, and a method for manufacturing circuit wiring. Background Technology
[0002] Since the number of steps required to obtain the specified pattern is small, the following method is widely used: a photosensitive composition layer is deposited on a substrate or other transfer object using a transfer film, and the photosensitive composition layer is exposed through a mask and then developed.
[0003] For example, Patent Document 1 discloses a photosensitive film (transfer film) for manufacturing color filters.
[0004] Previous technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 6-324210 Summary of the Invention
[0007] The technical problem to be solved by the invention
[0008] In recent years, there has been a demand for further improvements in the performance of transfer films. Specifically, when the surface of the transfer film opposite to the temporary support is brought into contact with the substrate for bonding, it is required that wrinkles not easily form.
[0009] Based on the results of the inventors' research on the characteristics of the transfer film described in Patent Document 1, etc., it was found that wrinkles occur during lamination, which requires further improvement.
[0010] Therefore, the objective of this invention is to provide a transfer film that is less prone to wrinkling when it is adhered to the substrate.
[0011] Furthermore, the present invention also aims to provide a method for manufacturing a laminate using a transfer film and a method for manufacturing circuit wiring.
[0012] means for solving technical problems
[0013] As a result of in-depth research on the above-mentioned issues, the inventors discovered that the above-mentioned issues can be solved by the following configuration.
[0014] [1] A transfer film, which is a strip-shaped transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support,
[0015] The storage modulus Ea1 of the short side of the temporary support at 100°C relative to the storage modulus E of the long side of the temporary support at 100°C a2 The ratio is below 1.40.
[0016] [2] According to the transfer film described in [1], wherein,
[0017] X obtained from equation (1) is below 7.00%.
[0018] X = {〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 Formula (1) × 100
[0019] E a1 Storage modulus (GPa) of the temporary support at 100°C along its short side.
[0020] E a2 Storage modulus (GPa) of the temporary support at 100°C along its long side.
[0021] E b1 Storage modulus (GPa) of the temporary support at 80°C along its short side.
[0022] E b2 Storage modulus (GPa) of the temporary support at 80°C along its long side.
[0023] [3] According to the transfer film described in [1] or [2], wherein,
[0024] Storage modulus E of temporary support in the short direction at 100°C a1 Storage modulus E of the temporary support in the long direction at 100°C a2 The geometric mean is above 1.00 GPa.
[0025] [4] The transfer film according to any one of [1] to [3], wherein the thickness of the temporary support is 40.0 μm or less.
[0026] [5] The transfer film according to any one of [1] to [4], wherein the thickness of the photosensitive composition layer is 20.0 μm or less.
[0027] [6] The transfer film according to any one of [1] to [5], wherein,
[0028] The photosensitive composition layer comprises an adhesive polymer, a polymeric compound, and a polymerization initiator.
[0029] [7] The transfer film according to any one of [1] to [6] further comprises a refractive index adjustment layer disposed on the photosensitive composition layer.
[0030] [8] The transfer film according to any one of [1] to [7], wherein,
[0031] The photosensitive composition layer is used to form an electrode protective film for touch panels.
[0032] [9] A method for manufacturing a laminate, comprising:
[0033] In the bonding process, the surface of the transfer film of any one of [1] to [8] opposite to the temporary support is bonded to the transfer body to obtain a transfer body having a transfer body, a photosensitive composition layer and a temporary support in sequence.
[0034] The exposure process involves patterning the photosensitive composition layer; and
[0035] The developing process involves developing the exposed photosensitive composition layer to form a pattern;
[0036] The manufacturing method of the laminate also includes:
[0037] The peeling process involves peeling a temporary support from the substrate with the photosensitive composition layer between the bonding process and the exposure process, or between the exposure process and the developing process.
[0038]
[10] A method for manufacturing circuit wiring, comprising:
[0039] In the bonding process, the surface of the transfer film of any one of [1] to [8] opposite to the temporary support is bonded to the transfer body containing the conductive layer to obtain a transfer body having the transfer body, the photosensitive composition layer and the temporary support in sequence.
[0040] The exposure process involves patterning the photosensitive composition layer.
[0041] The developing process involves developing the exposed photosensitive composition layer to form a pattern; and
[0042] The etching process involves etching the conductive layer in areas where no pattern is configured.
[0043] The manufacturing methods for circuit wiring also include:
[0044] The peeling process involves peeling a temporary support from the substrate with the photosensitive composition layer between the bonding process and the exposure process, or between the exposure process and the developing process.
[0045]
[11] According to the method for manufacturing the laminated body described in [9], wherein,
[0046] The substrate to be transferred is a substrate with a stepped difference.
[0047] Invention Effects
[0048] According to the present invention, a transfer film that is less prone to wrinkling when bonded to a substrate can be provided. Furthermore, according to the present invention, a method for manufacturing a laminate using the transfer film and a method for manufacturing circuit wiring can also be provided. Attached Figure Description
[0049] Figure 1 This is a cross-sectional schematic diagram showing an example of a substrate with a stepped difference. Detailed Implementation
[0050] The present invention will now be described in detail.
[0051] In this specification, the numerical range indicated by “~” refers to the range including the values recorded before and after “~” as the lower and upper limits.
[0052] In this specification, within a range of numerical values described in stages, the upper or lower limit value recorded within a certain range can be replaced by the upper or lower limit value of other ranges of numerical values described in stages. Furthermore, within a range of numerical values described in this specification, the upper or lower limit value recorded within a certain range can also be replaced by the value shown in the embodiments.
[0053] In this specification, the term "process" includes not only independent processes, but also processes that achieve the intended purpose of the process, even if they cannot be clearly distinguished from other processes.
[0054] In this specification, "transparent" means that the average transmittance of visible light with a wavelength of 400-700nm is 80% or more, preferably 90% or more.
[0055] In this specification, the average transmittance of visible light is a value measured by a spectrophotometer, for example, a Hitachi, Ltd. spectrophotometer U-3310.
[0056] Unless otherwise specified in this specification, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) are values converted using polystyrene as a standard substance as determined by gel permeation chromatography (GPC) using three TSK gel SuperHZM-N (manufactured by Tosoh Corporation) columns connected in series, THF (tetrahydrofuran) as the eluent, a differential refractometer as the detector, and polystyrene as the standard substance.
[0057] Unless otherwise specified, the molecular weight of compounds with molecular weight distribution in this specification is the weight-average molecular weight.
[0058] Unless otherwise specified, the refractive index in this specification is the value measured using an ellipsometer under light at a wavelength of 550 nm.
[0059] In this specification, "(meth)acrylic acid" includes both acrylic acid and methacrylic acid, "(meth)acrylate" includes both acrylate and methacrylate, and "(meth)acryloyloxy" includes both acryloyloxy and methacryloyloxy.
[0060] Furthermore, in this specification, "organic group" refers to a group containing at least one carbon atom.
[0061] In this specification, there are no particular limitations on the type, position, or number of substituents when the phrase "may have substituents" is used. The number of substituents can be, for example, one, two, three, or more. Examples of substituents include monovalent nonmetallic groups other than hydrogen atoms, such as those selected from the following substituent T.
[0062] (Substituent T)
[0063] Examples of substituents T include, for example, halogen atoms such as fluorine, chlorine, bromine, and iodine; alkoxy groups such as methoxy, ethoxy, and tert-butoxy; aryloxy groups such as phenoxy and p-tolyloxy; alkoxycarbonyl groups such as methoxycarbonyl, butoxycarbonyl, and phenoxycarbonyl; acyloxy groups such as acetoxy, propionyloxy, and benzoyloxy; acyl groups such as acetyl, benzoyl, isobutyryl, acryloyl, methacryloyl, and methoxyoxalyl; alkylthioalkyl groups such as methylthioalkyl and tert-butylthioalkyl; arylthioalkyl groups such as phenylthioalkyl and p-tolylthioalkyl; alkyl; cycloalkyl; aryl; heteroaryl; hydroxyl; carboxyl; formyl; sulfonyl; cyano; nitro; ether; alkylaminocarbonyl; arylaminocarbonyl; sulfonamide; silyl; amino; monoalkylamino; dialkylamino; arylamino; and combinations thereof.
[0064] [Transfer film]
[0065] A transfer film is a strip-shaped transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support.
[0066] A strip shape refers to a transfer film whose length in one direction is longer than its length in another direction orthogonal to that direction. That is, the transfer film has a long side direction along the machine direction and a short side direction along the width direction.
[0067] As a characteristic feature of the transfer film of the present invention, as described below, the transfer film has a temporary support having a specified energy storage modulus.
[0068] Based on their research into conventional transfer films, the inventors discovered that wrinkles easily form when the surface of the transfer film opposite to the temporary support is brought into contact with the substrate and laminated. In contrast, it was found that in this invention, when a transfer film using a temporary support with a specified energy storage modulus is used, wrinkles are less likely to form.
[0069] The mechanism by which wrinkles are suppressed is not yet clear, but it is speculated that by using temporary supports with low anisotropy during lamination, the bonding can be more uniform, resulting in less wrinkling. Hereinafter, in this specification, the situation where wrinkles are less likely to occur will also be referred to as the superior effect of the present invention.
[0070] The following is a detailed description of the structure of the transfer film.
[0071] <Temporary support>
[0072] The transfer film has a temporary support.
[0073] Storage modulus E of the temporary support in the short side direction at 100°C a1 Storage modulus E at 100°C relative to the long side of the temporary support a2 The ratio (E) a1 / E a2 The lower limit is 1.40 or less. From the perspective of better effects of the present invention, it is preferable to be 1.35 or less, more preferably 1.30 or less, further preferably 1.25 or less, especially preferably 1.20 or less, and most preferably 1.10 or less. There is no particular limitation on the lower limit, but it is preferable to be 0.10 or more, more preferably 0.50 or more, further preferably 0.80 or more, and especially preferably 1.00 or more.
[0074] In addition, the temporary support, which supports the photosensitive composition layer described later, is eventually removed by a peeling process.
[0075] In the temporary support, X, as determined by equation (1), is preferably 8.00% or less, more preferably 7.00% or less, even more preferably 6.80% or less, and especially preferably 6.70% or less.
[0076] X = {〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 Formula (1) × 100
[0077] E a1 Storage modulus (GPa) of the temporary support at 100°C along its short side.
[0078] E a2Storage modulus (GPa) of the temporary support at 100°C along its long side.
[0079] E b1 Storage modulus (GPa) of the temporary support at 80°C along its short side.
[0080] E b2 Storage modulus (GPa) of the temporary support at 80°C along its long side.
[0081] Storage modulus E of the temporary support in the short side direction at 100°C a1 The preferred range is 1.00–5.00 GPa, more preferably 2.00–4.00 GPa, even more preferably 2.00–2.95 GPa, particularly preferably 2.50–2.90 GPa, and most preferably 2.50–2.70 GPa.
[0082] Storage modulus E of the temporary support at 100°C along its long side a2 The preferred range is 1.00–5.00 GPa, more preferably 2.00–4.00 GPa, even more preferably 2.15–3.00 GPa, particularly preferably 2.20–2.80 GPa, and most preferably 2.30–2.60 GPa.
[0083] Storage modulus E of the temporary support in the short direction at 80°C b1 The preferred range is 1.00–5.00 GPa, more preferably 3.00–5.00 GPa, even more preferably 3.50–4.65 GPa, especially preferably 3.50–4.50 GPa, and most preferably 4.00–4.40 GPa.
[0084] Storage modulus E of the temporary support at 80°C along its long side b2 The preferred range is 1.00–5.00 GPa, more preferably 2.00–4.00 GPa, even more preferably 3.18–4.00 GPa, especially preferably 3.25–4.00 GPa, and most preferably 3.30–3.80 GPa.
[0085] The aforementioned energy storage modulus can be measured, for example, using a dynamic viscoelasticity measuring device (Vibron: DVA-225 (manufactured by IT Measurement & Control Co., Ltd.)).
[0086] Storage modulus E of temporary support in the short direction at 100°C a1 Storage modulus E of the temporary support in the long direction at 100°C a2 The geometric mean is preferably 1.00 GPa or higher, more preferably 2.00 GPa or higher, and even more preferably 2.40 GPa or higher. There is no particular upper limit, but it is preferably 5.00 GPa or lower, and more preferably 3.00 GPa or lower.
[0087] Additionally, the geometric mean is the nth power of the product of all n values. For example, it is E. a1 With E a2 The square root of the product of (geometric mean = √(E)) a1 ×E a2 )).
[0088] To achieve the above-mentioned characteristics of the temporary support ((E) a1 / E a2 There are no particular limitations to the methods (e.g., biaxially stretched resin films, biaxially stretched polyethylene terephthalate films) used as temporary supports, and the above-mentioned characteristics can be achieved by adjusting the stretch ratios in the longitudinal and transverse directions.
[0089] The temporary support is preferably a membrane, and more preferably a resin membrane.
[0090] As a temporary support, a flexible membrane that does not undergo significant deformation, shrinkage, or stretching under pressure or under pressure and heat can be used.
[0091] Examples of such films include polyethylene terephthalate (PET) films (e.g., biaxially stretched polyethylene terephthalate films), cellulose triacetate films, polystyrene films, polyimide films, and polycarbonate films.
[0092] As a temporary support, a biaxially stretched polyethylene terephthalate film is preferred. Furthermore, the film used as a temporary support is preferably free from deformation such as wrinkles and scratches.
[0093] From the perspective of being able to expose patterns through a temporary support, the temporary support preferably has high transparency and a transmittance of 365nm light of 60% or more, more preferably 70% or more.
[0094] From the perspective of pattern formation properties during pattern exposure through a temporary support and the transparency of the temporary support, the haze of the temporary support is preferably low. Specifically, the haze value of the temporary support is preferably 2% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. There is no particular limitation on the lower limit, but 0% or more is preferred.
[0095] Considering the pattern formation properties and transparency of the temporary support during pattern exposure, the number of particles, foreign objects, and defects contained in the temporary support is preferably low. The number of particles, foreign objects, and defects with a diameter of 1 μm or larger is preferably 50 per 10 mm. 2 Below, 10 pieces / 10mm is preferred. 2 Below, 3 / 10mm are further preferred. 2The following is particularly preferred: 0 / 10mm 2 .
[0096] The thickness of the temporary support is not particularly limited, and is often below 200.0 μm. However, considering the superior performance of the present invention, it is preferable to be below 100.0 μm, more preferably below 40.0 μm, further preferably below 30.0 μm, especially preferably below 25.0 μm, and most preferably below 20.0 μm. The lower limit is not particularly limited, but is preferably above 1.0 μm, more preferably above 10.0 μm.
[0097] The thickness of the temporary support can be calculated as the average of any five points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0098] From a processability perspective, a layer containing microparticles (lubricant layer) can also be provided on the surface of the temporary support. The lubricant layer can be provided on one side or both sides of the temporary support.
[0099] The diameter of the particles contained in the lubricant layer is preferably 0.05 to 0.8 μm.
[0100] The thickness of the lubricant layer is preferably 0.05 to 1.0 μm.
[0101] Examples of temporary supports include biaxially stretched polyethylene terephthalate films with a thickness of 25.0 μm, 16.0 μm, and 12.0 μm.
[0102] As a preferred method for a temporary support, for example, paragraphs
[0017] to
[0018] of Japanese Patent Application Publication No. 2014-085643, paragraphs
[0019] to
[0026] of Japanese Patent Application Publication No. 2016-027363, paragraphs
[0041] to
[0057] of WO2012 / 081680A1 and paragraphs
[0029] to
[0040] of WO2018 / 179370A1 are cited, the contents of which are incorporated into this specification.
[0103] <Photosensitive Composite Layer>
[0104] The transfer film has a photosensitive composition layer disposed on a temporary support.
[0105] The photosensitive composition layer preferably comprises the adhesive polymer, polymerizable compound and polymerization initiator described later.
[0106] By transferring a photosensitive composition layer onto a substrate and then exposing and developing it, a pattern can be formed on the substrate.
[0107] As a photosensitive composition layer, it can be a positive photosensitive composition layer or a negative photosensitive composition layer.
[0108] A positive photosensitive composition layer refers to a photosensitive composition layer in which the solubility of the exposed portion in the developer increases due to exposure. A negative photosensitive composition layer refers to a photosensitive composition layer in which the solubility of the exposed portion in the developer decreases due to exposure.
[0109] Preferably, a negative photosensitive composition layer is used. When the photosensitive composition layer is a negative photosensitive composition layer, the resulting pattern is equivalent to a protective film.
[0110] From the perspective of coatability, the thickness of the photosensitive composition layer is preferably 20.0 μm or less, more preferably 15.0 μm or less, and even more preferably 10.0 μm or less. There are no particular limitations on the above lower limits, but it is preferably 0.05 μm or more, more preferably 3.0 μm or more, even more preferably 4.0 μm or more, and particularly preferably 5.0 μm or more.
[0111] The thickness of the photosensitive composition layer was calculated as the average of five arbitrary points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0112] The refractive index of the photosensitive composition layer is preferably 1.47 to 1.56, more preferably 1.49 to 1.54.
[0113] The photosensitive composition layer is preferably colorless. The a of the photosensitive composition layer... * The preferred value is -1.0 to 1.0, and the b value of the photosensitive composition layer is... * The preferred value is -1.0 to 1.0.
[0114] The hue of the photosensitive composition layer can be determined using a colorimeter (CR-221, manufactured by Minolta Co., Ltd.).
[0115] The NCO value of the photosensitive composition layer is preferably greater than 0.50 mmol / g, more preferably 0.55 mmol / g or more, and even more preferably 0.60 mmol / g or more.
[0116] The upper limit of the NCO value of the photosensitive composition layer is preferably 1.0 mmol / g or less, more preferably less than 0.80 mmol / g, and even more preferably less than 0.70 mmol / g.
[0117] The NCO value of the photosensitive composition layer refers to the number of moles of isocyanate groups contained in 1g of the photosensitive composition layer, which is a value calculated based on the structural formula of the capped isocyanate compound.
[0118] The following describes the materials that constitute the photosensitive composition layer.
[0119] [Adhesive Polymer]
[0120] The photosensitive composition layer may contain an adhesive polymer.
[0121] Examples of adhesive polymers, such as I, include (meth)acrylic resins, styrene resins, epoxy resins, polyamide resins, polyamide epoxy resins, alkyd resins, phenolic resins, polyester resins, polyurethane resins, epoxy acrylate resins obtained by reacting epoxy resins with (meth)acrylic acid, and acid-modified epoxy acrylate resins obtained by reacting epoxy acrylate resins with acid anhydrides.
[0122] As one of the preferred adhesive polymers, (meth)acrylic resins are an example, considering their excellent alkali developability and film-forming properties.
[0123] Furthermore, in this specification, (meth)acrylic resin refers to a resin having structural units derived from (meth)acrylic acid compounds. The content of structural units derived from (meth)acrylic acid compounds relative to all structural units of the (meth)acrylic acid resin is preferably 50% by mass or more, more preferably 70% by mass or more.
[0124] (Meth)acrylic resins may consist solely of structural units derived from (meth)acrylic acid compounds, or they may contain structural units derived from polymerizable monomers other than (meth)acrylic acid compounds. Specifically, the upper limit of the content of structural units derived from (meth)acrylic acid compounds is preferably 100% by mass or less relative to all structural units of the (meth)acrylic resin.
[0125] Examples of (meth)acrylic acid compounds include, for example, (meth)acrylic acid, (meth)acrylate, (meth)acrylamide, and (meth)acrylonitrile.
[0126] Examples of (meth)acrylates include, for example, alkyl (meth)acrylates, tetrahydrofurfuryl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, glycidyl (meth)acrylate, benzyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, and 2,2,3,3-tetrafluoropropyl (meth)acrylate, with alkyl (meth)acrylates being preferred.
[0127] Examples of (meth)acrylamides include, for example, diacetone acrylamide and other acrylamides.
[0128] Examples of alkyl methacrylates include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, undecyl methacrylate, and dodecyl methacrylate, which are alkyl methacrylates having 1 to 12 carbon atoms.
[0129] As (meth)acrylates, alkyl (meth)acrylates having alkyl groups having 1 to 4 carbon atoms are preferred, and methyl (meth)acrylate or ethyl (meth)acrylate are more preferred.
[0130] (Meth)acrylic resins can have structural units other than those derived from (meth)acrylic acid compounds.
[0131] As the polymerizable monomer that forms the above-mentioned structural unit, there are no particular restrictions as long as it is a compound other than (meth)acrylic acid compound that can copolymerize with (meth)acrylic acid compound. Examples include styrene compounds such as styrene, vinyltoluene and α-methylstyrene that can have substituents at the α-position or on the aromatic ring, vinyl alcohol esters such as acrylonitrile and vinyl-n-butyl ether, maleic acid, maleic anhydride, maleic acid monomethyl ester, maleic acid monoethyl ester and maleic acid monoisopropyl ester, fumaric acid, cinnamic acid, α-cyanocinonic acid, itaconic acid and crotonic acid.
[0132] These polymerizable monomers can be used in one or in combination of two or more.
[0133] Furthermore, from the perspective of further improving alkaline developability, (meth)acrylic resin preferably contains structural units having acid groups. Examples of acid groups include carboxyl, sulfonyl, phosphate, and phosphonic acid groups.
[0134] The (meth)acrylic resin more preferably contains a structural unit having a carboxyl group, and even more preferably has a structural unit derived from the above-mentioned (meth)acrylic acid.
[0135] From the perspective of excellent developability, the content of structural units having acid groups (preferably structural units derived from (meth)acrylic acid) in the (meth)acrylic resin is preferably 10% by mass or more relative to the total mass of the (meth)acrylic resin. Furthermore, there is no particular upper limit, but from the perspective of excellent alkali resistance, it is preferably 50% by mass or less, more preferably 40% by mass or less.
[0136] Furthermore, the (meth)acrylic resin is more preferably composed of structural units derived from the aforementioned alkyl (meth)acrylic esters.
[0137] The content of structural units derived from alkyl methacrylates in (meth)acrylic resins is preferably 50-90% by mass, more preferably 60-90% by mass, and even more preferably 65-90% by mass, relative to all structural units of (meth)acrylic resins.
[0138] As a (meth)acrylic resin, a resin having both structural units derived from (meth)acrylic acid and structural units derived from (meth)acrylic alkyl esters is preferred, and a resin consisting only of structural units derived from (meth)acrylic acid and structural units derived from (meth)acrylic alkyl esters is more preferred.
[0139] Furthermore, as a (meth)acrylic resin, an acrylic resin having structural units derived from methacrylic acid, structural units derived from methyl methacrylate, and structural units derived from ethyl acrylate is preferred.
[0140] Furthermore, from the viewpoint of further enhancing the effects of the present invention, the (meth)acrylic resin preferably has at least one structural unit selected from methacrylic acid and structural units derived from alkyl methacrylates, and preferably has both structural units derived from methacrylic acid and structural units derived from alkyl methacrylates.
[0141] From the perspective of further enhancing the effects of the present invention, the total content of structural units derived from methacrylic acid and structural units derived from alkyl methacrylates in the (meth)acrylic resin is preferably 40% by mass or more, more preferably 60% by mass or more, relative to all structural units of the (meth)acrylic resin. There is no particular upper limit, and it can be 100% by mass or less, preferably 80% by mass or less.
[0142] Furthermore, from the viewpoint of further enhancing the effects of the present invention, the (meth)acrylic resin preferably has at least one structural unit selected from methacrylic acid and structural units selected from alkyl methacrylates, and at least one structural unit selected from acrylic acid and structural units selected from alkyl acrylates.
[0143] From the perspective of further improving the effects of the present invention, the total content of structural units derived from methacrylic acid and structural units derived from alkyl methacrylates is preferably 60 / 40 to 80 / 20 by mass relative to the total content of structural units derived from acrylic acid and structural units derived from alkyl acrylates.
[0144] From the perspective of excellent developability of the photosensitive composition layer after transfer, (meth)acrylic resin preferably has ester groups at the ends.
[0145] Furthermore, the terminal portion of the (meth)acrylic resin is composed of a site derived from the polymerization initiator used in its synthesis. (Meth)acrylic resins with ester groups at the terminals are synthesized using a polymerization initiator that generates free radicals containing ester groups.
[0146] Furthermore, alkali-soluble resins are another preferred type of adhesive polymer.
[0147] In addition, in this invention, "alkali solubility" means that the solubility is 0.1g or more in 100g of a 1% by mass aqueous solution of sodium carbonate at 22°C.
[0148] For example, from the perspective of developability, the adhesive polymer is preferably an adhesive polymer with an acid value of 60 mg KOH / g or higher.
[0149] Furthermore, for example, from the viewpoint of easily forming a strong film by heating and thermal crosslinking with the crosslinking components, the adhesive polymer is more preferably a carboxyl-containing resin with an acid value of 60 mg KOH / g or higher (so-called carboxyl-containing resin), and even more preferably a carboxyl-containing (meth)acrylic resin with an acid value of 60 mg KOH / g or higher (so-called carboxyl-containing (meth)acrylic resin).
[0150] When the adhesive polymer is a resin containing carboxyl groups, thermal crosslinking can be performed by adding thermally crosslinking compounds such as end-capped isocyanates, thereby increasing the three-dimensional crosslinking density. Furthermore, if the carboxyl groups of the resin are dehydrated and hydrophobic, the resistance to damp heat can be improved.
[0151] As for carboxyl-containing (meth)acrylic resins with an acid value of 60 mg KOH / g or higher, there are no particular restrictions as long as the above acid value condition is met, and they can be appropriately selected from known (meth)acrylic resins.
[0152] For example, acrylic resins containing carboxyl groups in polymers with an acid value of 60 mg KOH / g or higher, as described in paragraph
[0025] of Japanese Patent Application Publication No. 2011-095716, and acrylic resins containing carboxyl groups in polymers with an acid value of 60 mg KOH / g or higher, as described in paragraphs
[0033] to
[0052] of Japanese Patent Application Publication No. 2010-237589, are preferred.
[0153] Other preferred types of adhesive polymers include styrene-acrylic acid copolymers.
[0154] Furthermore, in this invention, styrene-acrylic acid copolymer refers to a resin having structural units derived from styrene compounds and structural units derived from (meth)acrylic acid compounds. The total content of the aforementioned structural units derived from styrene compounds and structural units derived from (meth)acrylic acid compounds, relative to all structural units of the copolymer, is preferably 30% by mass or more, more preferably 50% by mass or more. There is no particular limitation on the lower limit, but 100% by mass or less is preferred.
[0155] Furthermore, the content of structural units derived from styrene compounds relative to all structural units of the aforementioned copolymer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 5 to 80% by mass.
[0156] Furthermore, the content of the structural units derived from the (meth)acrylic acid compound is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20 to 95% by mass, relative to all structural units of the copolymer.
[0157] From the perspective of further improving the effects of the present invention, the adhesive polymer preferably has an aromatic ring structure, and more preferably contains structural units having an aromatic ring structure.
[0158] Examples of monomers that form structural units with aromatic ring structures include styrene compounds such as styrene, tert-butoxystyrene, methylstyrene, and α-methylstyrene, as well as benzyl methacrylate.
[0159] Among them, styrene compounds are preferred, and styrene is more preferred.
[0160] Furthermore, from the viewpoint of further enhancing the effects of the present invention, the adhesive polymer more preferably has a structural unit represented by the following formula (S) (a structural unit derived from styrene).
[0161] [Chemical Formula 1]
[0162]
[0163] When the adhesive polymer contains structural units having aromatic ring structures, from the perspective of further enhancing the effects of the present invention, the content of structural units having aromatic ring structures relative to all structural units of the adhesive polymer is preferably 5 to 90% by mass, more preferably 10 to 70% by mass, and even more preferably 20 to 60% by mass.
[0164] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of the structural unit having an aromatic ring structure in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 60 mol%, relative to all structural units of the adhesive polymer.
[0165] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of the structural unit represented by the above formula (S) in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 60 mol%, relative to all structural units of the adhesive polymer.
[0166] Furthermore, in this invention, when the content of "structural unit" is specified by molar ratio, the meaning of "structural unit" is the same as that of "monomer unit." Moreover, in this invention, the "monomer unit" can be modified after polymerization via polymer reactions, etc. The same applies hereinafter.
[0167] From the perspective of further enhancing the effects of the present invention, the adhesive polymer preferably has a monocyclic aliphatic hydrocarbon ring structure or a polycyclic aliphatic hydrocarbon ring structure. That is, the adhesive polymer preferably contains structural units having a monocyclic or polycyclic aliphatic hydrocarbon ring structure. More preferably, the adhesive polymer has a polycyclic aliphatic hydrocarbon ring structure, and even more preferably, it has a ring structure formed by the fusion of two or more aliphatic hydrocarbon rings.
[0168] Examples of rings that constitute aliphatic hydrocarbon ring structures include tricyclic decane rings, cyclohexane rings, cyclopentane rings, norbornene rings, and isophorone rings.
[0169] In particular, considering the superior effects of the present invention, a ring formed by the fusion of two or more aliphatic hydrocarbon rings is preferred, and a tetrahydrodicyclopentadiene ring (tricyclic [5.2.1.0]) is more preferred. 2,6 [decane ring].
[0170] Examples of monomers that form structural units with aliphatic hydrocarbon ring structures include dicyclopentyl methacrylate, cyclohexyl methacrylate, and isobornyl methacrylate.
[0171] Furthermore, from the perspective of further superior effects of the present invention, the adhesive polymer more preferably has a structural unit represented by the following formula (Cy), and more preferably has a structural unit represented by the above formula (S) and a structural unit represented by the following formula (Cy).
[0172] [Chemical Formula 2]
[0173]
[0174] In equation (Cy), R M R represents a hydrogen atom or a methyl group. Cy This indicates a monovalent group having an aliphatic hydrocarbon ring structure.
[0175] R in equation (Cy) M Methyl is preferred.
[0176] From the perspective of achieving better results in this invention, R in formula (Cy) Cy Preferably, it is a monovalent group with an aliphatic hydrocarbon ring structure having 5 to 20 carbon atoms, more preferably a monovalent group with an aliphatic hydrocarbon ring structure having 6 to 16 carbon atoms, and even more preferably a monovalent group with an aliphatic hydrocarbon ring structure having 8 to 14 carbon atoms.
[0177] Furthermore, R as in equation (Cy) Cy The aliphatic hydrocarbon ring structure in the structure can be a monocyclic aliphatic hydrocarbon ring structure or a polycyclic aliphatic hydrocarbon ring structure. For better performance of the invention, a monocyclic aliphatic hydrocarbon ring structure such as a cyclopentane ring structure, a cyclohexane ring structure, or an isophorone ring structure, or a polycyclic aliphatic hydrocarbon ring structure such as a tetrahydrodicyclopentadiene ring structure or a norbornene ring structure, is preferred. A cyclohexane ring structure or a tetrahydrodicyclopentadiene ring structure is more preferred, and a tetrahydrodicyclopentadiene ring structure is even more preferred.
[0178] Furthermore, considering the superior effects of the present invention, R of formula (Cy) Cy The aliphatic hydrocarbon ring structure in the form is preferably a polycyclic aliphatic hydrocarbon ring, more preferably a ring structure formed by the fusion of two or more aliphatic hydrocarbon rings, and even more preferably a ring structure formed by the fusion of two to four aliphatic hydrocarbon rings.
[0179] Furthermore, considering the superior effects of the present invention, R in formula (Cy) Cy Preferably, the oxygen atom of -C(=0)0- in formula (Cy) is a group that is directly bonded to an aliphatic hydrocarbon ring structure (which can be monocyclic or polycyclic), i.e., an aliphatic hydrocarbon cyclic group, more preferably cyclohexyl or dicyclopentyl, and even more preferably dicyclopentyl.
[0180] The adhesive polymer may have one structural unit with an aliphatic hydrocarbon ring structure, or it may have two or more structural units.
[0181] When the adhesive polymer contains structural units having an aliphatic hydrocarbon ring structure, from the perspective of further improving the effects of the present invention, the content of structural units having an aliphatic hydrocarbon ring structure relative to all structural units of the adhesive polymer is preferably 5 to 90% by mass, more preferably 10 to 80% by mass, and even more preferably 20 to 70% by mass.
[0182] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of structural units having aliphatic hydrocarbon ring structures in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 50 mol%, relative to all structural units of the adhesive polymer.
[0183] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of the structural unit represented by the above formula (Cy) in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 50 mol%, relative to all structural units of the adhesive polymer.
[0184] When the adhesive polymer contains structural units having aromatic ring structures and structural units having aliphatic hydrocarbon ring structures, from the perspective of further improving the effects of the present invention, the total content of structural units having aromatic ring structures and structural units having aliphatic hydrocarbon ring structures relative to all structural units of the adhesive polymer is preferably 10 to 90% by mass, more preferably 20 to 80% by mass, and even more preferably 40 to 75% by mass.
[0185] Furthermore, from the viewpoint of achieving even better results from the present invention, the total content of structural units having aromatic ring structures and structural units having aliphatic hydrocarbon ring structures in the adhesive polymer is preferably 10 to 80 mol%, more preferably 20 to 70 mol%, and even more preferably 40 to 60 mol%, relative to all structural units of the adhesive polymer.
[0186] Furthermore, from the perspective of further superior effects of the present invention, the total content of the structural units represented by the above formula (S) and the structural units represented by the above formula (Cy) in the adhesive polymer is preferably 10 to 80 mol%, more preferably 20 to 70 mol%, and even more preferably 40 to 60 mol% relative to all structural units of the adhesive polymer.
[0187] Furthermore, from the perspective of further superior effects of the present invention, the molar amount nS of the structural unit represented by the above formula (S) and the molar amount nCy of the structural unit represented by the above formula (Cy) in the adhesive polymer preferably satisfy the relationship shown in the following formula (SCy), more preferably satisfy the relationship shown in the following formula (SCy-1), and even more preferably satisfy the relationship shown in the following formula (SCy-2).
[0188] 0.2≤nS / (nS+nCy)≤0.8 Formula (SCy)
[0189] 0.30≤nS / (nS+nCy)≤0.75 formula (SCy-1)
[0190] 0.40≤nS / (nS+nCy)≤0.70 formula (SCy-2)
[0191] From the perspective of further advantages of the present invention, the adhesive polymer preferably contains structural units having acid groups.
[0192] Examples of acid groups include carboxyl, sulfonyl, phosphonic acid, and phosphate groups, with carboxyl being the most preferred.
[0193] As the above-mentioned structural unit having an acid group, the structural unit derived from (meth)acrylic acid as shown below is preferred, and the structural unit derived from methacrylic acid is more preferred.
[0194] [Chemical Formula 3]
[0195]
[0196] The adhesive polymer may contain one structural unit with an acid group, or it may contain two or more structural units.
[0197] When the adhesive polymer contains structural units with acid groups, from the perspective of further improving the effects of the present invention, the content of structural units with acid groups relative to all structural units of the adhesive polymer is preferably 5 to 50% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 30% by mass.
[0198] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of the structural units having acid groups in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 50 mol%, and even more preferably 20 to 40 mol%, relative to all structural units of the adhesive polymer.
[0199] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of structural units derived from (meth)acrylic acid in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 50 mol%, and even more preferably 20 to 40 mol%, relative to all structural units of the adhesive polymer.
[0200] From the perspective of further improving the effects of the present invention, the adhesive polymer preferably has reactive groups, and more preferably contains structural units having reactive groups.
[0201] As reactive groups, free radical polymerizable groups are preferred, and olefinically unsaturated groups are more preferred. Furthermore, when the adhesive polymer has olefinically unsaturated groups, the adhesive polymer preferably contains structural units with olefinically unsaturated groups in the side chains.
[0202] In this invention, "main chain" refers to the longest bonded chain in the molecule of the polymer compound that constitutes the resin, and "side chain" refers to the atomic group that branches off from the main chain.
[0203] As an olefinic unsaturated group, (meth)acrylic acid group is preferred, and (meth)acryloyloxy group is more preferred.
[0204] Examples of structural units with reactive groups include those shown below, but are not limited to these.
[0205] [Chemical Formula 4]
[0206]
[0207] Adhesive polymers may contain one structural unit with a reactive group, or they may contain two or more.
[0208] When the adhesive polymer contains structural units with reactive groups, from the viewpoint of further improving the effects of the present invention, the content of structural units with reactive groups relative to all structural units of the adhesive polymer is preferably 5 to 70% by mass, more preferably 10 to 50% by mass, and even more preferably 20 to 40% by mass.
[0209] Furthermore, from the viewpoint of achieving even better results from the present invention, the content of structural units having reactive groups in the adhesive polymer is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 50 mol%, relative to all structural units of the adhesive polymer.
[0210] As a method for introducing reactive groups into adhesive polymers, one example is the reaction of compounds such as epoxy compounds, terminal isocyanate compounds, isocyanate compounds, vinyl sulfone compounds, aldehyde compounds, hydroxymethyl compounds, and carboxylic anhydrides with functional groups such as hydroxyl, carboxyl, primary amino, secondary amino, acetoacetyl, and sulfonyl groups.
[0211] As a preferred example of a method for introducing reactive groups into an adhesive polymer, a method can be described as follows: after synthesizing a polymer having carboxyl groups through a polymerization reaction, glycidyl (meth)acrylate reacts with a portion of the carboxyl groups of the obtained polymer through a polymer reaction, thereby introducing (meth)acryloyloxy groups into the polymer. By this method, an adhesive polymer having (meth)acryloyloxy groups in its side chains can be obtained.
[0212] The polymerization reaction described above is preferably carried out at a temperature of 70–100°C, more preferably at a temperature of 80–90°C. As the polymerization initiator used in the above polymerization reaction, an azo initiator is preferred; for example, more preferably, V-601 (trade name) or V-65 (trade name) manufactured by FUJIFILM Wako Pure Chemical Corporation. The above polymer reaction is preferably carried out at a temperature of 80–110°C. In the above polymer reaction, a catalyst such as an ammonium salt is preferably used.
[0213] As the adhesive polymer, the polymers shown below are preferred for better performance of the present invention. Furthermore, the content ratios (a to d) and weight-average molecular weight Mw of each structural unit shown below can be appropriately changed according to the purpose.
[0214] [Chemical Formula 5]
[0215]
[0216] [Chemical Formula 6]
[0217]
[0218] Furthermore, the adhesive polymer may comprise a polymer (hereinafter also referred to as "polymer X") containing structural units having a carboxylic anhydride structure.
[0219] The carboxylic anhydride structure can be either a chain-like carboxylic anhydride structure or a cyclic carboxylic anhydride structure, preferably a cyclic carboxylic anhydride structure.
[0220] The ring in the cyclic carboxylic anhydride structure is preferably a 5- to 7-membered ring, more preferably a 5- or 6-membered ring, and even more preferably a 5-membered ring.
[0221] The structural unit having a carboxylic anhydride structure is preferably a structural unit in which a divalent group obtained by removing two hydrogen atoms from a compound represented by the following formula P-1 is included in the main chain, or a structural unit in which a monovalent group obtained by removing one hydrogen atom from a compound represented by the following formula P-1 is directly or via a divalent linker bonded to the main chain.
[0222] [Chemical Formula 7]
[0223]
[0224] In equation P-1, R A1a Indicates substituent, n 1a RA 1a They can be the same or different, Z 1a This indicates a divalent group forming a ring containing -C(=0)-O-C(=0)-, n 1a Represents integers greater than or equal to 0.
[0225] As a result of R A1a The substituents are represented, for example, alkyl groups.
[0226] As Z 1a Preferably, the alkylene group has 2 to 4 carbon atoms, more preferably it has 2 or 3 carbon atoms, and even more preferably it has 2 carbon atoms.
[0227] n 1a Represents integers greater than or equal to 0. In Z... 1a When representing alkylene groups with 2 to 4 carbon atoms, n 1a Preferably, it is an integer from 0 to 4, more preferably an integer from 0 to 2, and even more preferably 0.
[0228] n 1a When representing integers greater than 2, there exist multiple R values. A1aThey can be the same or different. Furthermore, there can be multiple R values. A1a They can bond together to form a ring, but it is preferable that they do not bond together to form a ring.
[0229] As a structural unit having a carboxylic anhydride structure, a structural unit derived from an unsaturated carboxylic anhydride is preferred, a structural unit derived from an unsaturated cyclic carboxylic anhydride is more preferred, a structural unit derived from an unsaturated aliphatic cyclic carboxylic anhydride is even more preferred, a structural unit derived from maleic anhydride or itaconic anhydride is particularly preferred, and a structural unit derived from maleic anhydride is most preferred.
[0230] The following are specific examples of structural units having a carboxylic anhydride structure, but structural units having a carboxylic anhydride structure are not limited to these specific examples. In the structural units described below, Rx represents a hydrogen atom, a methyl group, a CH2OH group, or a CF3 group, and Me represents a methyl group.
[0231] [Chemical Formula 8]
[0232]
[0233] [Chemical Formula 9]
[0234]
[0235] The structural units with carboxylic anhydride structures in polymer X can be a single type or two or more types.
[0236] The total content of structural units having a carboxylic anhydride structure relative to all structural units of polymer X is preferably 0 to 60 mol%, more preferably 5 to 40 mol%, and even more preferably 10 to 35 mol%.
[0237] The photosensitive composition layer may contain only one polymer X, or it may contain two or more polymers.
[0238] When the photosensitive composition layer contains polymer X, from the viewpoint of further enhancing the effects of the present invention, the content of polymer X relative to the total mass of the photosensitive composition layer is preferably 0.10 to 30.00% by mass, more preferably 0.20 to 20.00% by mass, even more preferably 0.20 to 5.00% by mass, and particularly preferably 0.50 to 1.50% by mass.
[0239] From the viewpoint of further enhancing the effects of the present invention, the weight-average molecular weight (Mw) of the adhesive polymer is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 10,000 to 50,000, and particularly preferably 10,000 to 30,000.
[0240] From the perspective of reducing developer residue, the dispersion of the binder polymer (weight average molecular weight Mw / number average molecular weight Mn) is preferably 1.0 to 3.0, more preferably 2.0 to 3.0.
[0241] The acid value of the adhesive polymer is preferably 10-200 mg KOH / g, more preferably 60-200 mg KOH / g, even more preferably 60-150 mg KOH / g, and especially preferably 60-110 mg KOH / g.
[0242] The acid value of the adhesive polymer was determined according to the method described in JIS K0070:1992.
[0243] The photosensitive composition layer may contain only one type of adhesive polymer, or it may contain two or more types.
[0244] From the perspective of further superior effects of the present invention, the content of the adhesive polymer relative to the total mass of the photosensitive composition layer is preferably 10.00 to 90.00% by mass, more preferably 30.00 to 80.00% by mass, even more preferably 40.00 to 70.00% by mass, and particularly preferably 45.00 to 60.00% by mass.
[0245] [Polymerization initiator]
[0246] The photosensitive composition layer may contain a polymerization initiator.
[0247] There are no particular restrictions on the polymerization initiator; any known polymerization initiator can be used. Photopolymerization initiators are preferred.
[0248] Examples of polymerization initiators include, for instance, photopolymerization initiators having an oxime ester structure (hereinafter also referred to as "oxime-based photopolymerization initiators"), photopolymerization initiators having an α-aminoalkylphenyl ketone structure (hereinafter also referred to as "α-aminoalkylphenyl ketone-based photopolymerization initiators"), photopolymerization initiators having an α-hydroxyalkylphenyl ketone structure (hereinafter also referred to as "α-hydroxyalkylphenyl ketone-based photopolymerization initiators"), photopolymerization initiators having an acylphosphine oxide structure (hereinafter also referred to as "acylphosphine oxide-based photopolymerization initiators"), and photopolymerization initiators having an N-phenylglycine structure (hereinafter also referred to as "N-phenylglycine-based photopolymerization initiators").
[0249] The polymerization initiator preferably includes at least one selected from oxime-based photopolymerization initiators, α-aminoalkylphenyl ketone-based photopolymerization initiators, α-hydroxyalkylphenyl ketone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators; more preferably, it includes at least one selected from oxime-based photopolymerization initiators, α-aminoalkylphenyl ketone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators; and even more preferably, it includes at least one selected from oxime-based photopolymerization initiators and α-aminoalkylphenyl ketone-based photopolymerization initiators.
[0250] As polymerization initiators, examples include those described in paragraphs
[0031] to
[0042] of Japanese Patent Application Publication No. 2011-95716 and paragraphs
[0064] to
[0081] of Japanese Patent Application Publication No. 2015-014783.
[0251] Examples of polymerization initiators include 1-[4-(phenylthio)]phenyl-1,2-octanedione-2-(O-benzoyl oxime) [trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] acetophenone-1-(O-acetyl oxime) [trade name: IRGACURE (registered trademark) OXE-02, manufactured by BASF], and 8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)- 11H-Benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methyl ketone-(O-acetyl oxime) [trade name: IRGACURE (registered trademark) OXE-03, manufactured by BASF], 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methyl-1-pentanone-1-(O-acetyl oxime) [trade name: IRGACURE (registered trademark) OXE-04, manufactured by BASF], oxime ester compounds [trade name: Lunar (registered trademark) 6, DKSH] [Japan K.K. Manufacturing], 1-[4-(phenylthio)phenyl]-3-cyclopentylprop-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-305, manufactured by Changzhou Tronly New Electronic Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazole-3-yl]-,2-(O-acetyl oxime) (trade name: TR-PBG-326, manufactured by Changzhou Tronly New Electronic Materials Co., Ltd.) (manufactured by Co., Ltd.), 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazole-3-yl)-prop-1,2-dione-2-(0-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Tronly New Electronic Materials Co., Ltd.), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad (registered trademark) 379EG, manufactured by IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinylprop-1-one (trade name: Omnirad (registered trademark) 907, manufactured by IGM Resins BV). [BV manufactured], 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylprop-1-one [trade name: Omnirad (registered trademark) 127, IGM Resins BV][Production], 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-butanone-1 [trade name: Omnirad (registered trademark) 369, manufactured by IGM Resins BV], 2-hydroxy-2-methyl-1-phenyl-prop-1-one [trade name: Omnirad (registered trademark) 1173, manufactured by IGM Resins BV], 1-hydroxycyclohexylphenyl ketone [trade name: Omnirad (registered trademark) 184, manufactured by IGM Resins BV], 2,2-dimethoxy-1,2-diphenylethyl-1-one [trade name: Omnirad 651, manufactured by IGM Resins BV], 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and (1-(biphenyl-4-yl)-2-methyl-2-morpholinylprop-1-one (trade name: APi-307, manufactured by Shenzhen UV-ChemTech Ltd.)).
[0252] Polymerization initiators can be used alone or in combination with two or more.
[0253] The content of polymerization initiator in the photosensitive composition layer is not particularly limited, but it is preferably 0.10% by mass or more, more preferably 0.50% by mass or more, relative to the total mass of the photosensitive composition layer. There is no particular upper limit, but it is preferably 10.00% by mass or less, more preferably 5.00% by mass or less, relative to the total mass of the photosensitive composition layer.
[0254] [Polymerizing compounds]
[0255] The photosensitive composition layer may contain polymeric compounds.
[0256] Polymerizable compounds are compounds having polymerizable groups. Examples of polymerizable groups include free radical polymerizable groups and cationic polymerizable groups, with free radical polymerizable groups being preferred.
[0257] The polymerizable compound preferably comprises a free radical polymerizable compound having an olefin unsaturated group (hereinafter also referred to as "olefin unsaturated compound").
[0258] As an olefinic unsaturated group, (meth)acryloyloxy is preferred.
[0259] In this specification, the olefinic unsaturated compound is a compound other than the aforementioned adhesive polymer, and its molecular weight is preferably less than 5,000.
[0260] As polymerizable compounds, compounds represented by the following formula (M) are preferred (also simply referred to as "compound M").
[0261] Q 2 -R 1a-Q 1 Formula (M)
[0262] In formula (M), Q 1 and Q 2 Each independently represents (meth)acryloyloxy, R 1 This represents a divalent linker with a chain-like structure.
[0263] Regarding Q in equation (M) 1 and Q 2 From the perspective of ease of synthesis, Q 1 and Q 2 Preferably, they are the same group.
[0264] Furthermore, considering reactivity, Q in equation (M) 1 and Q 2 Acryloyloxy is preferred.
[0265] As R in equation (M) 1a From the perspective of achieving better results in this invention, alkylene or alkoxyalkylene (-L) is preferred. 1 -OL 1 _) or polyalkoxyalkylene(-(L 1 -O) p -L l _), more preferably a hydrocarbon group or polyalkoxyalkylene group with 2 to 20 carbon atoms, even more preferably an alkylene group with 4 to 20 carbon atoms, and especially preferably a straight-chain alkylene group with 6 to 18 carbon atoms.
[0266] The hydrocarbon group mentioned above may have a chain structure in at least a portion. There are no particular restrictions on the portion other than the chain structure. For example, it may be any one of branched, cyclic, or straight-chain alkylene, aryl, ether bond, and combinations thereof with 1 to 5 carbon atoms. Preferably, it is an alkylene group or a group composed of two or more alkylene groups and one or more aryl groups. More preferably, it is an alkylene group. Even more preferably, it is a straight-chain alkylene group.
[0267] In addition, the above L 1 Each alkyl group is independently represented, preferably vinyl, propenyl, or butenyl, more preferably vinyl or 1,2-propenyl. p represents an integer of 2 or more, preferably an integer from 2 to 10.
[0268] Furthermore, considering the superior effects of the present invention, the compound M is connected to Q. 1 With Q 2 The shortest connecting chain between atoms preferably has 3 to 50 atoms, more preferably 4 to 40 atoms, even more preferably 6 to 20 atoms, and especially preferably 8 to 12 atoms.
[0269] In this invention, "connection Q"1 With Q 2 "Number of atoms in the shortest link chain between Q" refers to the number of atoms in the shortest link chain between Q and Q. 1 Connected R 1 The atoms in Q are connected to 2 Connected R 1 The shortest number of atoms up to the atoms in the array.
[0270] Examples of compound M include, for instance, 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, hydrogenated bisphenol F di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. These ester monomers can also be used as mixtures.
[0271] In view of further improving the effects of the present invention, the compound M is preferably at least one compound selected from 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate and neopentyl glycol di(meth)acrylate, more preferably at least one compound selected from 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate, and even more preferably at least one compound selected from 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate.
[0272] Furthermore, as a polymerizable compound, an olefinic unsaturated compound with two or more functions is preferred.
[0273] In this specification, "a 2 or more functional olefin unsaturated compound" refers to a compound having two or more olefin unsaturated groups in one molecule.
[0274] As an olefinic unsaturated group in an olefinic unsaturated compound, (meth)acryloyl group is preferred.
[0275] As an olefinic unsaturated compound, (meth)acrylate compounds are preferred.
[0276] As a difunctional olefinic unsaturated compound, there are no particular restrictions, and it is possible to appropriately select from known compounds.
[0277] Examples of difunctional olefinic unsaturated compounds other than compound M mentioned above include tricyclodecanediethanol di(meth)acrylate and tricyclodecanediethanol di(meth)acrylate.
[0278] As a difunctional olefinic unsaturated compound, polymeric compound B1, which contains an aromatic ring and two olefinic unsaturated groups, is also preferred.
[0279] When the photosensitive composition layer contains polymeric compound B1, from the viewpoint of superior resolution, the mass ratio of polymeric compound B1 content to the total mass of the polymeric compound is preferably 40% or more, more preferably 50% or more, further preferably 55% or more, and particularly preferably 60% or more. There is no particular upper limit, but from the viewpoint of peelability, it is, for example, 100% or less, preferably 99% or less, more preferably 95% or less, further preferably 90% or less, and particularly preferably 85% or less.
[0280] The aromatic rings present in the polymerizable compound B1 include, for example, aromatic hydrocarbon rings such as benzene rings, naphthalene rings, and anthracene rings, aromatic heterocycles such as thiophene rings, furan rings, pyrrole rings, imidazole rings, triazole rings, and pyridine rings, as well as their fused rings, preferably aromatic hydrocarbon rings, and more preferably benzene rings. Furthermore, the aforementioned aromatic rings may have substituents.
[0281] Polymerizable compound B1 may have only one aromatic ring or more than two aromatic rings.
[0282] From the viewpoint of improving resolution by suppressing the swelling of the photosensitive composition layer caused by the developer, polymeric compound B1 preferably has a bisphenol structure.
[0283] Examples of bisphenol structures include, for example, the bisphenol A structure derived from bisphenol A (2,2-bis(4-hydroxyphenyl)propane), the bisphenol F structure derived from bisphenol F (2,2-bis(4-hydroxyphenyl)methane), and the bisphenol B structure derived from bisphenol B (2,2-bis(4-hydroxyphenyl)butane), with the bisphenol A structure being preferred.
[0284] As a polymeric compound B1 having a bisphenol structure, examples include compounds having a bisphenol structure and two polymeric groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure.
[0285] The two ends of the bisphenol structure can be directly bonded to two polymerizable groups, or they can be bonded through one or more alkene oxygen groups. As the alkene oxygen groups added to the two ends of the bisphenol structure, ethyleneoxy or propenoxy are preferred, and ethyleneoxy is more preferred. There is no particular limitation on the number of alkene oxygen groups added to the bisphenol structure, but 4 to 16 are preferred per molecule, and 6 to 14 are more preferred.
[0286] Regarding polymeric compound B1 having a bisphenol structure, it is described in paragraphs 0072 to 0080 of Japanese Patent Application Publication No. 2016-224162, the contents of which are incorporated herein by reference.
[0287] As the polymerizable compound B1, a difunctional olefinic unsaturated compound having a bisphenol A structure is preferred, and 2,2-bis(4-((meth)acryloyloxypolyalkoxy)phenyl)propane is more preferred.
[0288] Examples of 2,2-bis(4-((meth)acryloyloxypolyalkoxy)phenyl)propane include, for instance, 2,2-bis(4-(methacryloyloxydiethoxy)phenyl)propane (FA-324M, manufactured by Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloyloxyethoxypropoxy)phenyl)propane, 2,2-bis(4-(methacryloyloxypentaethoxy)phenyl)propane (BPE-500, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), 2,2-bis(4-(methacryloyloxydodecylethoxytetrapropoxy)phenyl)propane (FA-3200MY, manufactured by Hitachi Chemical Co., Ltd.), and 2,2-bis(4-(methacryloyloxypentadecaethoxy)phenyl)propane (BPE-1300, manufactured by SHIN-NAKAMURA CHEMICAL). 2,2-bis(4-(methacryloyloxydiethoxy)phenyl)propane (BPE-200, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.) and ethoxylated (10) bisphenol A diacrylate (NK ESTER A-BPE-10, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0289] As a polymerizable compound B1, a compound represented by the following general formula (B1) is also preferred.
[0290] [Chemical Formula 10]
[0291]
[0292] In general formula B1, R1 and R2 independently represent a hydrogen atom or a methyl group, respectively. A represents C2H4. B represents C3H6. n1 and n3 are each independently integers from 1 to 39, and n1+n3 is an integer from 2 to 40. n2 and n4 are each independently integers from 0 to 29, and n2+n4 is an integer from 0 to 30. The arrangement of the structural units -(AO)- and -(BO)- can be random or block. Moreover, in the case of block, either -(AO)- or -(BO)- can be on the diphenyl side.
[0293] In one embodiment, n1+n2+n3+n4 is preferably 2 to 20, more preferably 2 to 16, and even more preferably 4 to 12. Furthermore, n2+n4 is preferably 0 to 10, more preferably 0 to 4, even more preferably 0 to 2, and particularly preferably 0.
[0294] Polymer compound B1 can be used alone or in combination with two or more compounds.
[0295] When the photosensitive composition layer contains polymerizable compound B1, from the viewpoint of superior resolution, its content relative to the total mass of the photosensitive composition layer is preferably 10% by mass or more, more preferably 20% by mass or more. There is no particular upper limit, but from the viewpoint of transferability and edge melting (the phenomenon of photosensitive resin seeping out from the end of the transfer part), it is preferably 70% by mass or less, more preferably 60% by mass or less.
[0296] Commercially available examples of difunctional olefinic unsaturated compounds include, for example, tricyclodecanediethanol diacrylate (trade name: NK ESTER A-DCP, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), tricyclodecanediethanol dimethacrylate (trade name: NK ESTER DCP, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), 1,9-nonanediol diacrylate (trade name: NKESTER A-NOD-N, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), and 1,6-hexanediol diacrylate (trade name: NK ESTER A-HD-N, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0297] As an olefinic unsaturated compound with more than three functions, there are no particular restrictions, and it is possible to appropriately select from known compounds.
[0298] Examples of olefinic unsaturated compounds with three or more functions include dipentaerythritol (tris / tetras / penta / hexa)methacrylate, pentaerythritol (tris / tetra)methacrylate, trimethylolpropane tri(meth)acrylate, di-trimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds with a glycerol tri(meth)acrylate skeleton.
[0299] Here, "(tri / tetra / penta / hexa)meth)acrylate" is a concept that includes tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate, and "(tri / tetra)meth)acrylate" is a concept that includes tri(meth)acrylate and tetra(meth)acrylate.
[0300] Examples of polymerizable compounds include, for instance, caprolactone-modified (meth)acrylate compounds (such as KAYARAD DPCA-20 manufactured by Nippon Kayaku Co., Ltd. and A-9300-1CL manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), epoxy-modified (meth)acrylate compounds (such as KAYARAD R-604 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd., and EBECRYL 135 manufactured by DAICEL-ALLNEX LTD.), and ethoxylated glycerol triacrylates (such as NK ESTER A-GLY-9E manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0301] Examples of polymerizable compounds include urethane (meth)acrylate compounds [preferably urethane (meth)acrylate compounds with three or more functions].
[0302] Examples of urethane (meth)acrylate compounds with three or more functions include 8UX-015A (manufactured by Taisi Fine Chemical Co., Ltd.), NK ESTER UA-32P (manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), and NK ESTER UA-1100H (manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0303] As polymerizable compounds, olefinic unsaturated compounds having acid groups are preferred.
[0304] Examples of acid groups include phosphate, sulfonate, and carboxyl groups.
[0305] Among them, the carboxyl group is preferred as the acid group.
[0306] Examples of olefinic unsaturated compounds with acid groups include 3- to 4-functional olefinic unsaturated compounds with acid groups (formed by introducing carboxyl groups into the pentaerythritol tri- and tetraacrylate (PETA) backbone (acid value: 80-120 mg KOH / g)) and 5- to 6-functional olefinic unsaturated compounds with acid groups (formed by introducing carboxyl groups into the dipentaerythritol penta- and hexaacrylate (DPHA) backbone (acid value: 25-70 mg KOH / g)).
[0307] These trifunctional or higher olefinic unsaturated compounds with acid groups can also be used simultaneously with difunctional olefinic unsaturated compounds with acid groups, as needed.
[0308] As an olefinic unsaturated compound having an acid group, it is preferably selected from at least one of olefinic unsaturated compounds having a carboxyl group and a carboxylic anhydride thereof.
[0309] If the olefinic unsaturated compound with an acidic group is selected from at least one of olefinic unsaturated compounds with two or more functions having a carboxyl group and their carboxylic anhydrides, the reproducibility and film strength are further improved.
[0310] There are no particular restrictions on olefinic unsaturated compounds with more than two functions, including carboxyl groups, and appropriate selection can be made from known compounds.
[0311] Examples of olefinic unsaturated compounds with more than two functions, having a carboxyl group, include ARONIX (registered trademark) TO-2349 (manufactured by TOAGOSEI CO., LTD.), ARONIX (registered trademark) M-520 (manufactured by TOAGOSEI CO., LTD.), and ARONIX (registered trademark) M-510 (manufactured by TOAGOSEI CO., LTD.).
[0312] As an olefinic unsaturated compound having an acid group, the preferred polymeric compound having an acid group is the one described in paragraphs
[0025] to
[0030] of Japanese Patent Application Publication No. 2004-239942, the contents of which are incorporated herein by reference.
[0313] Examples of polymerizable compounds include, for instance, compounds obtained by reacting a polyol with an α,β-unsaturated carboxylic acid, compounds obtained by reacting a compound containing a glycidyl group with an α,β-unsaturated carboxylic acid, urethane monomers such as (meth)acrylate compounds having urethane bonds, phthalic acid compounds such as γ-chloro-β-hydroxypropyl-β'-(meth)acryloyloxyethyl-phthalate, β-hydroxyethyl-β'-(meth)acryloyloxyethyl-phthalate and β-hydroxypropyl-β'-(meth)acryloyloxyethyl-phthalate, and alkyl (meth)acrylates.
[0314] These can be used individually or in combination of two or more.
[0315] Examples of compounds obtained by reacting polyols with α,β-unsaturated carboxylic acids include, for example, bisphenol A-based (meth)acrylate compounds such as 2,2-bis(4-((meth)acryloyloxypolyethoxy)phenyl)propane, 2,2-bis(4-((meth)acryloyloxypolypropoxy)phenyl)propane, and 2,2-bis(4-((meth)acryloyloxypolyethoxypolypropoxy)phenyl)propane; polyethylene glycol di(meth)acrylate with 2 to 14 ethylene oxide alkyl groups; polyethylene glycol di(meth)acrylate with 2 to 14 propylene oxide alkyl groups; and polyethylene glycol di(meth)acrylate with 2 to 14 ethylene oxide alkyl groups and 2 to 14 propylene oxide alkyl groups. Acrylates, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxytri(meth)acrylate, trimethylolpropane diethoxytri(meth)acrylate, trimethylolpropane triethoxytri(meth)acrylate, trimethylolpropane tetraethoxytri(meth)acrylate, trimethylolpropane pentaethoxytri(meth)acrylate, di(trimethylolpropane)tetraacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0316] Among these compounds, olefinic unsaturated compounds having a tetrahydroxymethylmethane structure or a trihydroxymethylpropane structure are preferred, and tetrahydroxymethylmethane tri(meth)acrylate, tetrahydroxymethylmethane tetra(meth)acrylate, trihydroxymethylpropane tri(meth)acrylate or di(trihydroxymethylpropane)tetraacrylate are more preferred.
[0317] Examples of polymerizable compounds include, for instance, caprolactone-modified olefinic compounds (e.g., KAYARAD DPCA-20 manufactured by Nippon Kayaku Co., Ltd. and A-9300-1CL manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.), alkylene oxide-modified olefinic compounds (e.g., KAYARAD R-604 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd., and EBECRYL 135 manufactured by DAICEL-ALLNEX LTD.), and ethoxylated glycerol triacrylates (e.g., A-GLY-9E manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0318] Among these, the polymerizable compound (especially an olefinic unsaturated compound) preferably contains ester bonds, which is desirable for the photosensitive composition layer after transfer to have excellent developability.
[0319] As an olefinic unsaturated compound containing ester bonds, there are no particular limitations as long as the molecule contains ester bonds. From the perspective of the superior effect of the present invention, olefinic unsaturated compounds having a tetramethylolmethane structure or a trimethylolpropane structure are preferred, and tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate or di(trimethylolpropane)tetraacrylate are more preferred.
[0320] From the perspective of imparting reliability, as an olefinic unsaturated compound, it is preferable to include an olefinic unsaturated compound having an aliphatic group having 6 to 20 carbon atoms and an olefinic unsaturated compound having the above-mentioned tetrahydroxymethylmethane structure or trihydroxymethylpropane structure.
[0321] Examples of olefinic unsaturated compounds having an aliphatic structure with 6 or more carbon atoms include 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and tricyclodecanediethanol di(meth)acrylate.
[0322] Examples of polymerizable compounds include, for instance, polymerizable compounds having an aliphatic hydrocarbon ring structure (preferably difunctional olefinic unsaturated compounds).
[0323] As the aforementioned polymerizable compound, a polymerizable compound having a ring structure formed by the fusion of two or more aliphatic hydrocarbon rings (preferably a structure selected from tricyclodecane and tricyclodecene structures) is preferred, a difunctional olefinic unsaturated compound having a ring structure formed by the fusion of two or more aliphatic hydrocarbon rings is more preferred, and tricyclodecanediethanol di(meth)acrylate is even more preferred.
[0324] From the perspective of achieving better results in this invention, the preferred aliphatic hydrocarbon ring structures are cyclopentane, cyclohexane, tricyclodecane, tricyclodecene, norbornene, or isophorone.
[0325] The molecular weight of the polymerizable compound is preferably 200 to 3,000, more preferably 250 to 2,600, even more preferably 280 to 2,200, and especially preferably 300 to 2,200.
[0326] Relative to the total content of all polymeric compounds contained in the photosensitive composition layer, the proportion of polymeric compounds with a molecular weight of 300 or less among the polymeric compounds contained in the photosensitive composition layer is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0327] There is no particular limitation on the lower limit of the proportion of polymeric compounds with a molecular weight of less than 300, but it is preferred to be 1.0% by mass or more.
[0328] The photosensitive composition layer preferably contains olefinic unsaturated compounds with two or more functions, more preferably contains olefinic unsaturated compounds with three or more functions, and even more preferably contains olefinic unsaturated compounds with three or four functions.
[0329] The photosensitive composition layer preferably comprises a difunctional olefinic unsaturated compound having an aliphatic hydrocarbon ring structure and an adhesive polymer containing structural units having an aliphatic hydrocarbon ring.
[0330] Furthermore, the photosensitive composition layer preferably comprises a compound represented by formula (M) and an olefinic unsaturated compound having an acid group, more preferably comprising 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate and a polyfunctional olefinic unsaturated compound having a carboxylic acid group, and even more preferably a succinic acid modified form comprising 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate and dipentaerythritol pentaacrylate.
[0331] The photosensitive composition layer preferably comprises a compound represented by formula (M), an olefinic unsaturated compound having an acid group, and a thermally crosslinking compound described later; more preferably, it comprises a compound represented by formula (M), an olefinic unsaturated compound having an acid group, and a capped isocyanate compound described later.
[0332] The photosensitive composition layer preferably comprises a difunctional olefin unsaturated compound (preferably a difunctional (meth)acrylate compound) and a trifunctional or higher olefin unsaturated compound (preferably a trifunctional or higher (meth)acrylate compound).
[0333] From the perspective of rust prevention, the photosensitive composition layer preferably contains compound M and a difunctional olefinic unsaturated compound having an aliphatic hydrocarbon ring structure.
[0334] Furthermore, considering adhesion, suppression of developing residue, and rust prevention, the photosensitive composition layer preferably includes compound M and an olefin unsaturated compound having an acid group; more preferably, it includes compound M, a difunctional olefin unsaturated compound having an aliphatic hydrocarbon ring structure, and an olefin unsaturated compound having an acid group; even more preferably, it includes compound M, a difunctional olefin unsaturated compound having an aliphatic hydrocarbon ring structure, a trifunctional or higher olefin unsaturated compound, and an olefin unsaturated compound having an acid group; and most preferably, it includes compound M, a difunctional olefin unsaturated compound having an aliphatic hydrocarbon ring structure, a trifunctional or higher olefin unsaturated compound, an olefin unsaturated compound having an acid group, and a urethane (meth)acrylate compound.
[0335] Furthermore, considering adhesion, developer residue suppression, and rust prevention, the photosensitive composition layer preferably comprises 1,9-nonanediol diacrylate and a polyfunctional olefin unsaturated compound having a carboxylic acid group; more preferably, it comprises 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate, and a polyfunctional olefin unsaturated compound having a carboxylic acid group; even more preferably, it comprises 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate, dipentaerythritol hexaacrylate (A-DPH), and an olefin unsaturated compound having a carboxylic acid group; and especially preferably, it comprises 1,9-nonanediol diacrylate, tricyclodecanediethanol diacrylate, an olefin unsaturated compound having a carboxylic acid group, and a carbamate acrylate compound.
[0336] The photosensitive composition layer may contain a monofunctional olefin unsaturated compound as an olefin unsaturated compound.
[0337] The content of the olefinic unsaturated compounds with more than two functions in the above-mentioned olefinic unsaturated compounds is preferably 60 to 100% by mass, more preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass, relative to the total content of all olefinic unsaturated compounds contained in the photosensitive composition layer.
[0338] Polymerizable compounds (especially olefinic unsaturated compounds) can be used alone or in combination with two or more compounds.
[0339] The content of polymeric compounds (especially olefinic unsaturated compounds) in the photosensitive composition layer relative to the total mass of the photosensitive composition layer is preferably 1.00 to 70.00% by mass, more preferably 10.00 to 70.00% by mass, even more preferably 15.0 to 50.0% by mass, and particularly preferably 20.0 to 40.0% by mass.
[0340] [Heterocyclic compounds]
[0341] The photosensitive composition layer may contain heterocyclic compounds.
[0342] Heterocyclic compounds can have any heterocyclic ring, whether it is a monocyclic or polycyclic heterocyclic ring.
[0343] Examples of heteroatoms found in heterocyclic compounds include nitrogen, oxygen, and sulfur atoms. Heterocyclic compounds preferably have at least one atom selected from nitrogen, oxygen, and sulfur atoms, and more preferably have a nitrogen atom.
[0344] Examples of heterocyclic compounds include triazole compounds, benzotriazole compounds, tetraazole compounds, thiadiazole compounds, triazine compounds, razotanine compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, benzoxazole compounds, pyrimidine and pyridine compounds.
[0345] The heterocyclic compound is preferably selected from at least one compound selected from triazole compounds, benzotriazole compounds, tetraazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzimidazole compounds, benzoxazole compounds, and pyridine compounds, and more preferably selected from at least one compound selected from triazole compounds, benzotriazole compounds, tetraazole compounds, thiadiazole compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, and benzoxazole compounds.
[0346] The following are preferred examples of heterocyclic compounds.
[0347] The following compounds can be cited as examples of triazole and benzotriazole compounds.
[0348] [Chemical Formula 11]
[0349]
[0350] [Chemical Formula 12]
[0351]
[0352] The following compounds can be cited as examples of tetrazolium compounds.
[0353] [Chemical Formula 13]
[0354]
[0355] [Chemical Formula 14]
[0356]
[0357] The following compounds can be cited as examples of thiadiazole compounds.
[0358] [Chemical Formula 15]
[0359]
[0360] The following compounds can be cited as examples of triazine compounds.
[0361] [Chemical Formula 16]
[0362]
[0363] The following compounds can be cited as examples of cyclotannin compounds.
[0364] [Chemical Formula 17]
[0365]
[0366] The following compounds can be cited as examples of thiazole compounds.
[0367] [Chemical Formula 18]
[0368]
[0369] The following compounds can be cited as examples of benzothiazole compounds.
[0370] [Chemical Formula 19]
[0371]
[0372] The following compounds can be cited as examples of benzimidazole compounds.
[0373] [Chemical Formula 20]
[0374]
[0375] [Chemical Formula 21]
[0376]
[0377] The following compounds can be cited as examples of benzoxazole compounds.
[0378] [Chemical Formula 22]
[0379]
[0380] Examples of pyridine compounds include isonicotinic acid and isonicotinamide.
[0381] The photosensitive composition layer may contain a single heterocyclic compound or two or more heterocyclic compounds.
[0382] When the photosensitive composition layer contains a heterocyclic compound, the content of the heterocyclic compound relative to the total mass of the photosensitive composition layer is preferably 0.01 to 20.00% by mass, more preferably 0.10 to 10.00% by mass, even more preferably 0.10 to 5.00% by mass, and particularly preferably 0.10 to 1.00% by mass.
[0383] [Aliphatic thiols]
[0384] The photosensitive composition layer may contain aliphatic thiol compounds.
[0385] As an aliphatic thiol compound, a monofunctional aliphatic thiol compound or a polyfunctional aliphatic thiol compound (i.e., an aliphatic thiol compound with two or more functions) is preferred. Considering the adhesion of the formed pattern (especially the adhesion after exposure), a polyfunctional aliphatic thiol compound is more preferred.
[0386] In this specification, "polyfunctional aliphatic thiols" refers to aliphatic compounds having two or more thiol groups (also called "mercapto groups") within their molecules.
[0387] The molecular weight of the polyfunctional aliphatic thiol compound is preferably 100 or more, more preferably 100 to 1,500, and even more preferably 150 to 1,000.
[0388] As for the number of functional groups in a multifunctional aliphatic thiol compound, for example, considering the tightness of the formed pattern, 2 to 10 functional groups are preferred, 2 to 8 functional groups are more preferred, and 2 to 6 functional groups are even more preferred.
[0389] Examples of polyfunctional aliphatic thiols include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetra(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, and trimethylolpropionyloxyethyl thiocyanate. Propane tris(3-mercaptopropionate), pentaerythritol tetra(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate), ethylene glycol dithiopropionate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,2-ethylenedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethylthiol, meso-2,3-dimercaptosuccinic acid, and di(mercaptoethyl) ether.
[0390] Among them, as a polyfunctional aliphatic thiol compound, it is preferably selected from at least one compound selected from trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane and 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0391] Examples of monofunctional aliphatic thiols include 1-octylthiol, 1-dodecylthiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0392] The photosensitive composition layer may contain a single aliphatic thiol compound or two or more aliphatic thiol compounds.
[0393] When the photosensitive composition layer contains an aliphatic thiol compound, the content of the aliphatic thiol compound relative to the total mass of the photosensitive composition layer is preferably 5% by mass or more, more preferably 5 to 50% by mass, even more preferably 5 to 30% by mass, and particularly preferably 8 to 20% by mass.
[0394] [Thermocrosslinking compounds]
[0395] Considering the strength of the cured film and the adhesion of the uncured film, the photosensitive composition layer preferably contains a thermally crosslinking compound.
[0396] In addition, in this specification, the thermally crosslinked compounds having olefinic unsaturated groups described later are considered as thermally crosslinked compounds, rather than as olefinic unsaturated compounds.
[0397] Furthermore, the thermally crosslinking compound is a compound that is different from the components (adhesive polymer, polymerization initiator, and polymeric compound, etc.) contained in the aforementioned photosensitive composition layer.
[0398] Examples of thermally crosslinkable compounds include epoxy compounds, oxetane compounds, hydroxymethyl compounds, and end-capped isocyanate compounds.
[0399] Among these considerations, end-capped isocyanate compounds are preferred, taking into account both the strength of the cured film and the adhesion of the uncured film.
[0400] Since the capped isocyanate compound reacts with hydroxyl and carboxyl groups, there is a tendency for the hydrophilicity of the formed film to decrease and its function as a protective film to be enhanced, for example, when at least one of the adhesive polymers and the free radical polymerizable compounds having olefinic unsaturated groups has at least one hydroxyl and carboxyl group.
[0401] In addition, capped isocyanate compounds are defined as "compounds having a structure in which isocyanate groups of isocyanate are protected (so-called masked) by capping agents".
[0402] (First-terminated isocyanate compound)
[0403] The end-capped isocyanate compound preferably contains an end-capped isocyanate compound (hereinafter also referred to as "first end-capped isocyanate compound") with an end-capped isocyanate equivalent (hereinafter also referred to as "NCO value") of 4.5 mmol / g or more. This results in superior flexural resistance and also inhibits corrosion of the conductive layer.
[0404] The NCO value of the J-terminated isocyanate compound is 4.5 mmol / g or more, and more preferably 5.0 mmol / g or more, and even more preferably 5.3 mmol / g or more, for better performance of the present invention.
[0405] From the perspective of further improving the effects of the present invention, the upper limit of the NCO value of the first capped isocyanate compound is preferably 6.0 mmol / g or less, more preferably less than 5.8 mmol / g, and even more preferably less than 5.7 mmol / g.
[0406] The NCO value of the terminated isocyanate compound in this invention refers to the number of millomolars of terminated isocyanate groups contained in 1g of terminated isocyanate compound, which can be calculated by the following formula.
[0407] Formula: NCO value of a capped isocyanate compound = 1000 × (number of capped isocyanate groups in the molecule) / (molecular weight of the capped isocyanate compound)
[0408] The dissociation temperature of the first capped isocyanate compound is preferably 100–160°C, more preferably 110–150°C.
[0409] In this specification, "dissociation temperature of the terminal isocyanate compound" refers to the temperature of the endothermic peak accompanying the deprotection reaction of the terminal isocyanate compound when analyzed by DSC (Differential Scanning Calorimetry) using a differential scanning calorimeter. There are no particular limitations on the differential scanning calorimeter used; for example, a differential scanning calorimeter manufactured by Seiko Instruments Inc. (model: DSC6200) is preferred.
[0410] Examples of end-capping agents with a dissociation temperature of 100–160°C include active methylene compounds (such as dimalonates (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)) and oxime compounds (such as formaldehyde oxime, acetaldehyde oxime, acetone oxime, methyl ethyl ketone oxime, cyclohexanone oxime, etc., which have a structure represented by -C(=N-OH)- in the molecule). Among the above, oxime compounds are preferred as end-capping agents with a dissociation temperature of 100–160°C from the perspective of storage stability.
[0411] From the viewpoint of further enhancing the effects of the present invention, the first-terminated isocyanate compound preferably has a ring structure. Examples of ring structures include aliphatic hydrocarbon rings, aromatic hydrocarbon rings, and heterocycles; from the viewpoint of further enhancing the effects of the present invention, aliphatic hydrocarbon rings and aromatic hydrocarbon rings are preferred, and aliphatic hydrocarbon rings are more preferred.
[0412] Specific examples of aliphatic hydrocarbon rings include cyclopentane and cyclohexane rings, with cyclohexane rings being preferred.
[0413] Specific examples of aromatic hydrocarbon rings include benzene rings and naphthalene rings, with benzene rings being preferred.
[0414] As a specific example of a heterocyclic ring, the isocyanurate ring can be cited.
[0415] When the first-terminated isocyanate compound has a ring structure, the number of rings is preferably 1 to 2, more preferably 1, from the viewpoint of better performance of the present invention. Furthermore, when the first-terminated isocyanate compound contains a fused ring, the number of rings constituting the fused ring is counted; for example, the number of rings in a naphthalene ring is counted as 2.
[0416] From the perspective of the superior strength of the formed pattern and the superior effect of the present invention, the number of end-capped isocyanate groups in the first end-capped isocyanate compound is preferably 2 to 5, more preferably 2 to 3, and even more preferably 2.
[0417] From the viewpoint of further improving the effects of the present invention, the first end-capped isocyanate compound is preferably an end-capped isocyanate compound represented by formula Q.
[0418] B 1 -A 1 -L 1 -A 2 -B 2 Formula Q
[0419] In formula Q, B 1 and B 2 Each is independently represented by a capped isocyanate group.
[0420] The terminating isocyanate group is not particularly limited, but from the perspective of better performance of the present invention, it is preferred that the isocyanate group is terminated by an oxime compound, and more preferably that the isocyanate group is terminated by a methyl ethyl ketone oxime group (specifically, a group represented by *-NH-C(=O)-ON=C(CH3)-C2H5). * indicates a group related to A. 1 Or A 2 The bonding location.
[0421] B 1 and B 2 Preferably, the groups have the same structure.
[0422] In formula Q, A 1 and A 2 Each can be independently represented as a single bond or an alkylene group having 1 to 10 carbon atoms, preferably an alkylene group having 1 to 10 carbon atoms.
[0423] The alkylene group can be linear, branched, or cyclic, preferably linear.
[0424] The alkylene group has 1 to 10 carbon atoms, preferably 1 to 5, more preferably 1 to 3, and even more preferably 1, for better results of the present invention.
[0425] A 1 and A 2 Preferably, the groups have the same structure.
[0426] In formula Q, L 1 This indicates a divalent linker.
[0427] As a specific example of a divalent linker, a divalent hydrocarbon group can be cited.
[0428] Specific examples of divalent hydrocarbon groups include divalent saturated hydrocarbon groups, divalent aromatic hydrocarbon groups, and groups formed by the linkage of two or more of these groups.
[0429] The divalent saturated hydrocarbon group can be linear, branched, or cyclic; for better performance of the invention, a cyclic form is preferred. For better performance of the invention, the divalent saturated hydrocarbon group preferably has 4 to 15 carbon atoms, more preferably 5 to 10, and even more preferably 5 to 8.
[0430] As a divalent aromatic hydrocarbon group, it is preferably composed of 5 to 20 carbon atoms; for example, phenylene can be cited. The divalent aromatic hydrocarbon group may have substituents (e.g., alkyl groups).
[0431] Among them, as a divalent linker, it is a group formed by linking a straight-chain, branched, or cyclic divalent saturated hydrocarbon group with 5 to 10 carbon atoms, or a cyclic saturated hydrocarbon group with 5 to 10 carbon atoms to a straight-chain alkylene group with 1 to 3 carbon atoms. Preferably, it is a divalent aromatic hydrocarbon group that may have substituents or a group formed by linking a divalent aromatic hydrocarbon group to a straight-chain alkylene group with 1 to 3 carbon atoms. More preferably, it is a cyclic divalent saturated hydrocarbon group with 5 to 10 carbon atoms or a phenylene group that may have substituents. Further preferably, it is a cyclohexylene group or a phenylene group that may have substituents. Especially preferably, it is a cyclohexylene group.
[0432] From the perspective of further improving the effects of the present invention, the end-capped isocyanate compound represented by formula Q is preferably the end-capped isocyanate compound represented by formula QA.
[0433] B 1a -A 1a -L 1a -A 2a -B 2a Formula QA
[0434] In formula QA, B 1a and B 2a Each is independently represented by a capped isocyanate group. B 1a and B 2a The preferred method and B in formula Q 1 and B 2 same.
[0435] In formula QA, A 1a and A 2a Each of these represents a divalent linker independently. A 1a and A 2a The preferred method for the divalent linker in formula Q is the same as that for A in formula Q. 1a and A 2a same.
[0436] In formula QA, L 1a It represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group.
[0437] L 1aThe number of carbon atoms in the cyclic divalent saturated hydrocarbon group is preferably 5 to 10, more preferably 5 to 8, even more preferably 5 to 6, and especially preferably 6.
[0438] L 1a The preferred method for the divalent aromatic hydrocarbon group in formula QA is the same as that for L in formula QA. 1 same.
[0439] Among them, L 1a The preferred group is a cyclic divalent saturated hydrocarbon group, more preferably a cyclic divalent saturated hydrocarbon group with 5 to 10 carbon atoms, even more preferably a cyclic divalent saturated hydrocarbon group with 5 to 10 carbon atoms, especially preferably a cyclic divalent saturated hydrocarbon group with 5 to 6 carbon atoms, and most preferably a cyclohexenyl group.
[0440] The following are specific examples of the first-terminated isocyanate compound, but the first-terminated isocyanate compound is not limited thereto.
[0441] [Chemical Formula 23]
[0442]
[0443] The photosensitive composition layer may contain a single first-terminated isocyanate compound or two or more first-terminated isocyanate compounds.
[0444] The content of the first capped isocyanate compound relative to the total mass of the photosensitive composition layer is preferably 0.50 to 25.00% by mass, more preferably 1.00 to 20.00% by mass, and even more preferably 1.50 to 5.00% by mass.
[0445] The first-terminated isocyanate compound is, for example, made by making a compound having an isocyanate group (e.g., B in the above formula Q). 1 and B 2 The compound (which is an isocyanate group) is obtained by reacting the isocyanate group of the compound with the above-mentioned capping agent.
[0446] (Second-terminated isocyanate compound)
[0447] The end-capped isocyanate compound preferably comprises an end-capped isocyanate compound with an NCO value of less than 4.5 mmol / g (hereinafter also referred to as "second end-capped isocyanate compound"). This allows for the suppression of development residue after patterning exposure and development of the photosensitive composition layer.
[0448] The NCO value of the second-terminated isocyanate compound is less than 4.5 mmol / g, preferably more than 2.0 mmol / g and less than 4.5 mmol / g, and more preferably 2.5 to 4.0 mmol / g.
[0449] The dissociation temperature of the second-terminated isocyanate compound is preferably 100–160°C, more preferably 110–150°C.
[0450] Specific examples of capping agents with a dissociation temperature of 100–160°C are described above.
[0451] Considering factors such as improving the film's brittleness or enhancing its adhesion to the substrate, the second end-capped isocyanate compound preferably has an isocyanurate structure. End-capped isocyanate compounds with an isocyanurate structure are obtained, for example, by isocyanuration of hexamethylene diisocyanate.
[0452] As a capped isocyanate compound having an isocyanurate structure, compounds with an oxime structure are preferred for use as capping agents because they make it easier to set the dissociation temperature within a preferred range and reduce development residue compared to compounds without an oxime structure.
[0453] Considering the strength of the formed pattern, the second-terminated isocyanate compound can have polymerizable groups. Preferably, free radical polymerizable groups are preferred as polymerizable groups.
[0454] Examples of polymerizable groups include olefinic unsaturated groups such as (meth)acryloyloxy, (meth)acrylamido, and styryl, as well as epoxy groups such as glycidyl. Among these, olefinic unsaturated groups are preferred, and (meth)acryloyloxy groups are more preferred, considering the surface texture, development speed, and reactivity of the obtained pattern.
[0455] The following are specific examples of the second-terminated isocyanate compound, but the second-terminated isocyanate compound is not limited thereto.
[0456] [Chemical Formula 24]
[0457]
[0458] Commercially available products can be used as the second-terminated isocyanate compound. Examples of commercially available products that are end-terminated isocyanate compounds include, for example, Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) AOI-BP, Karenz (registered trademark) MOI-BP, etc. (all manufactured by SHOWA DENKO KK), and end-terminated Duranate series (e.g., Duranate (registered trademark) TPA-B80E, manufactured by Asahi Kasei Corporation).
[0459] The photosensitive composition layer may contain a single second-terminated isocyanate compound or two or more second-terminated isocyanate compounds.
[0460] When the photosensitive composition layer contains a second-terminated isocyanate compound, the content of the second-terminated isocyanate compound relative to the total mass of the photosensitive composition layer is preferably 1.00 to 25.00% by mass, more preferably 1.00 to 20.0% by mass, and even more preferably 10.00 to 15.00% by mass, in order to further reduce the generation of development residue.
[0461] When the photosensitive composition layer includes a first end-capped isocyanate compound and a second end-capped isocyanate compound, considering the bending resistance and reduced moisture permeability, the mass ratio of the content of the first end-capped isocyanate compound to the content of the second end-capped isocyanate compound (first end-capped isocyanate compound / second end-capped isocyanate compound) is preferably 0.10 to 9.00, more preferably 0.18 to 2.35, and even more preferably 0.18 to 1.00.
[0462] A single thermally crosslinking compound can be used alone, or two or more compounds can be used simultaneously.
[0463] When the photosensitive composition layer contains a thermally crosslinking compound, the content of the thermally crosslinking compound relative to the total mass of the photosensitive composition layer is preferably 1.00 to 50.00% by mass, more preferably 10.00 to 30.00% by mass, and even more preferably 15.00 to 20.00% by mass.
[0464] [surfactant]
[0465] The photosensitive composition layer may contain a surfactant.
[0466] As surfactants, examples include those described in paragraph
[0017] of Japanese Patent No. 4502784 and paragraphs
[0060] to
[0071] of Japanese Unexamined Patent Application No. 2009-237362, the contents of which are incorporated herein by reference.
[0467] Examples of surfactants include fluorinated surfactants, silicone surfactants, and hydrocarbon surfactants, with fluorinated surfactants or silicone surfactants being preferred, and fluorinated surfactants being more preferred. Furthermore, nonionic surfactants are preferred as surfactants.
[0468] Commercially available fluorinated surfactants include, for example, MEGAFACE F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, EXP, MFS-578, EXP.M FS-578-2, EXP.MFS-579, EXP.MFS-586, EXP.MFS-587, EXP.MFS-628, EXP.MFS-631, EXP.MFS-603, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K and DS-21 (all of the above are from DICCorporation); Fluorad FC430, FC431 and FC171 (all of the above are from Sumitomo) 3MLimited); Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393 and KH-40 (all manufactured by AGC Inc.); PolyFox PF636, PF656, PF6320, PF6520 and PF7002 (all manufactured by OMNOVA Solutions Inc.); Ftergent 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC and 681 (all manufactured by Neos Corporation), U-120E (Uni-chem Co., Ltd.), etc.
[0469] Furthermore, fluorinated surfactants can preferably use acrylic compounds that have a molecular structure containing functional groups (including fluorine atoms) and, upon heating, partially break down the functional groups containing fluorine atoms, causing the fluorine atoms to volatilize. Examples of such fluorinated surfactants include the MEGAFACE DS series manufactured by DIC Corporation (The Chemical Daily Co., Ltd., February 22, 2016; NIKKEI BUSINESS DAILY, February 23, 2016, for example, MEGAFACDS-21).
[0470] Furthermore, fluorinated surfactants are preferably polymers of fluorinated vinyl ether compounds having fluorinated alkyl or fluorinated alkylene ether groups and hydrophilic vinyl ether compounds.
[0471] Fluorinated surfactants can also use block polymers. Fluorinated polymers are also preferred as fluorinated surfactants, comprising repeating units derived from (meth)acrylate compounds having fluorine atoms, and repeating units derived from (meth)acrylate compounds having two or more (preferably five or more) alkeneoxy groups (preferably ethoxy or propyleneoxy groups).
[0472] Fluorinated surfactants can also be used on fluoropolymers with olefinically unsaturated groups on their side chains. Examples include MEGAFACE RS-101, RS-102, RS-718K, and RS-72-K (all manufactured by DIC Corporation).
[0473] From the perspective of improving environmental adaptability, surfactants derived from alternative materials of straight-chain perfluoroalkyl compounds with 7 or more carbon atoms, such as perfluorooctane acid (PFOA) and perfluorooctane sulfonic acid (PFOS), are preferred as fluorinated surfactants.
[0474] Examples of silicone surfactants include linear polymers composed of siloxane bonds and modified siloxane polymers with organic groups introduced into the side chains or ends.
[0475] Commercially available silicone surfactants include EXP.S-309-2, EXP.S-315, EXP.S-503-2, EXP.S-505-2 (all manufactured by DIC Corporation), DOWSIL 8032 ADDITIVE, TORAY SILICONE DC3PA, TORAY SILICONE SH7PA, TORAY SILICONE DC11PA, TORAY SILICONE SH21PA, TORAY SILICONE SH28PA, TORAY SILICONE SH29PA, TORAY SILICONE SH30PA, and TORAY SILICONE SH8400 (all manufactured by Dow Corning Toray). Co., Ltd.); X-22-4952, -643, X-22-6191, 106. KP-109, KP-109, KP-112, KP-120, KP-121, KP-124, KP-125, KP-301, KP-306, KP-310, KP-322, KP-32 3. KP-327, KP-341, KP-368, KP-369, KP-611, KP-620, KP-621, KP-626, and KP-652 (the above are Shin-Etsu Silicone (manufactured by Co., Ltd.); F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (manufactured by Momentive Performance Materials Inc.); BYK307, BYK323, BYK330, BYK313, BYK315N, BYK331, BYK333, BYK345, BYK347, BYK348, BYK349, BYK370, BYK377, BYK378, and BYK323 (manufactured by BYK-Chemie GmbH).
[0476] Examples of hydrocarbon-based surfactants include, for example, glycerol, trimethylolpropane, trimethylolethane, and their ethoxylated and propoxylated derivatives (e.g., propoxyglycerol and ethoxyglycerol); polyoxyethylene lauryl ether, polyoxyethylene octadecyl ether, polyoxyethylene oil-based ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, and sorbitol fatty acid esters.
[0477] Commercially available hydrocarbon surfactants include: PLURONIC (registered trademark) L10, L31, L61, L62, 10R5, 17R2, 25R2 (all manufactured by BASF); TETRONIC 304, 701, 704, 901, 904 and 150R1 (all manufactured by BASF); SOLSPERSE 20000 (all manufactured by The Lubrizol Corporation); NCW-101, NCW-1001 and NCW-1002 (all manufactured by FUJIFILM Wako Pure Chemical Corporation); PIONIN D-6112, D-6112-W and D-6315 (all manufactured by TAKEMOTO OIL&FAT Co., Ltd.); OLFINE E1010, Surfynol 104, 400 and 440 (all manufactured by Nissin Chemical Industry Co., Ltd.).
[0478] Surfactants can be used alone or in combination with two or more.
[0479] When the photosensitive composition layer contains a surfactant, the surfactant content relative to the total mass of the photosensitive composition layer is preferably 0.01 to 3.0% by mass, more preferably 0.05 to 1.0% by mass, and even more preferably 0.10 to 0.80% by mass.
[0480] [Phosphate ester compounds]
[0481] The photosensitive composition layer may contain phosphate ester compounds.
[0482] As phosphate ester compounds, there are no particular restrictions as long as at least one of the three hydrogens in phosphoric acid (O=P(OH)3) is replaced by an organic group. Examples include the Phosmer series (Phosmer-M, Phosmer-CL, Phosmer-PE, Phosmer-MH, Phosmer-PP) manufactured by Uni-Chemical Co., Ltd., the KAYAMER series (KAYAMER PM-21, KAYAMER PM-2) manufactured by Nippon Kayaku Co., Ltd., and the LIGHT ESTER series (LIGHT ESTER P-2M (trade name)) manufactured by KYOE ISHA CHEMICAL Co., LTD.
[0483] Phosphate compounds can be used alone or in combination with two or more compounds.
[0484] The content of the phosphate ester compound is not particularly limited, but is preferably 0.05 to 3.0% by mass, more preferably 0.1 to 2.0% by mass, and even more preferably 0.2 to 1.0% by mass, relative to the total mass of the photosensitive composition layer.
[0485] When the photosensitive composition layer contains a phosphate ester compound, the content of the phosphate ester compound is not particularly limited. However, considering further improving the adhesion to the substrate, it is preferably 10 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by mass of the total adhesive polymer and polymeric compound. Furthermore, there is no particular upper limit to the above content, but it is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more.
[0486] [Polymerization Inhibitor]
[0487] The photosensitive composition layer may contain polymerization inhibitors.
[0488] Polymerization inhibitors are compounds that have the function of delaying or inhibiting polymerization reactions. For example, known compounds that are used as polymerization inhibitors can be used as polymerization inhibitors.
[0489] Examples of polymerization inhibitors include phenothiazine compounds such as bis-(1-dimethylbenzyl)phenothiazine and 3,7-dioctylphenothiazine; bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][vinylbis(oxyvinyl)]2,4-bis[(laurylthio)methyl]-o-cresol, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl), 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl), 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylaniline)-1,3,5- Hindered phenolic compounds such as triazine and pentaerythritol tetrakis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; nitroso compounds or their salts such as 4-nitrosophenol, N-nitrosodiphenylamine, N-nitrosocyclohexylhydroxyamine and N-nitrosophenylhydroxyamine; quinone compounds such as methylhydroquinone, tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone and 4-benzoquinone; phenolic compounds such as 4-methoxyphenol, 4-methoxy-1-naphthol and tert-butylcatechol; and metal salt compounds such as copper dibutyldithiocarbamate, copper diethyldithiocarbamate, manganese diethyldithiocarbamate and manganese diphenyldithiocarbamate.
[0490] Among them, as a polymerization inhibitor, it is preferably selected from at least one of phenothiazine compounds, nitroso compounds or their salts and hindered phenolic compounds, more preferably phenothiazine, bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][vinylbis(oxyvinyl)]2,4-bis[(laurylthio)methyl]-o-cresol, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) and N-nitrosophenylhydroxylamine aluminum salt.
[0491] Polymerization inhibitors can be used alone or in combination with two or more.
[0492] When the photosensitive composition layer contains a polymerization inhibitor, the content of the polymerization inhibitor relative to the total mass of the photosensitive composition layer is preferably 0.01 to 10.0% by mass, more preferably 0.05 to 5.00% by mass, and even more preferably 0.10 to 3.00% by mass.
[0493] [Hydrogen-donating compounds]
[0494] The photosensitive composition layer may contain a hydrogen-donating compound.
[0495] Hydrogen-donating compounds can further enhance the sensitivity of photopolymerization initiators to active light and inhibit the polymerization hindrance of polymerizable compounds by oxygen.
[0496] Examples of hydrogen-donating compounds include, for example, amines and amino acid compounds.
[0497] Examples of amines include compounds described in, for instance, the Journal of Polymer Society, Vol. 10, p. 3173 (1972), Japanese Patent Publication No. 44-020189, Japanese Patent Application Publication No. 51-082102, Japanese Patent Application Publication No. 52-134692, Japanese Patent Application Publication No. 59-138205, Japanese Patent Application Publication No. 60-084305, Japanese Patent Application Publication No. 62-018537, Japanese Patent Application Publication No. 64-033104, and Research Disclosure No. 33825. More specifically, examples include 4,4'-bis(diethylamino)benzophenone, tris(4-dimethylaminophenyl)methane (also known as colorless crystal violet), triethanolamine, ethyl p-dimethylaminobenzoate, p-formyldimethylaniline, and p-methylthiodimethylaniline.
[0498] In view of the superior effects of the present invention, the amine is preferably selected from at least one of 4,4'-bis(diethylamino)benzophenone and tris(4-dimethylaminophenyl)methane.
[0499] Examples of amino acid compounds include, for example, N-phenylglycine, N-methyl-N-phenylglycine and N-ethyl-N-phenylglycine.
[0500] In view of the superior effects of the present invention, N-phenylglycine is preferred as the amino acid compound.
[0501] Furthermore, examples of hydrogen-donating compounds include, for instance, organometallic compounds (such as tributyltin acetate) described in Japanese Patent Publication No. 48-042965, hydrogen donors described in Japanese Patent Publication No. 55-034414, and sulfur compounds (such as trithianes) described in Japanese Patent Application Publication No. 6-308727.
[0502] One hydrogen-donating compound can be used alone, or two or more can be used simultaneously.
[0503] When the photosensitive composition layer contains a hydrogen-donating compound, from the viewpoint of improving the curing speed by balancing the polymerization growth rate and chain transfer, the content of the hydrogen-donating compound relative to the total mass of the photosensitive composition layer is preferably 0.01 to 10.00% by mass, more preferably 0.03 to 8.00% by mass, and even more preferably 0.05 to 5.00% by mass.
[0504] [Residual monomers]
[0505] The photosensitive composition layer sometimes contains residual monomers of the structural units of the aforementioned adhesive polymer.
[0506] From the perspective of pattern formation and reliability, the content of residual monomers relative to the total mass of the adhesive polymer is preferably 5,000 ppm by mass or less, more preferably 2,000 ppm by mass or less, and even more preferably 500 ppm by mass or less. There is no particular limitation on the lower limit, but it is preferably 1 ppm by mass or more relative to the total mass of the adhesive polymer, more preferably 10 ppm by mass or more.
[0507] From the perspective of pattern formation and reliability, the residual monomers of each structural unit of the adhesive polymer relative to the total mass of the photosensitive composition layer are preferably 3,000 ppm by mass or less, more preferably 600 ppm by mass or less, and even more preferably 100 ppm by mass or less. There is no particular limitation on the lower limit, but relative to the total mass of the photosensitive composition layer, it is preferably 0.1 ppm by mass or more, more preferably 1 ppm by mass or more.
[0508] The residual monomer content of monomers during the synthesis of adhesive polymers via polymer reactions is preferably within the above-mentioned range. For example, when synthesizing adhesive polymers by reacting glycidyl acrylate with carboxylic acid side chains, the content of glycidyl acrylate is preferably within the above-mentioned range.
[0509] The amount of residual monomers can be determined by known methods such as liquid chromatography and gas chromatography.
[0510] [Other ingredients]
[0511] The photosensitive composition layer may contain components other than those described above (hereinafter also referred to as "other components"). Examples of other components include colorants, antioxidants, and particles (e.g., metal oxide particles). Furthermore, other additives described in paragraphs
[0058] to
[0071] of Japanese Patent Application Publication No. 2000-310706 may also be included as other components.
[0512] -particle-
[0513] As particles, metal oxide particles are preferred.
[0514] Metals in metal oxide particles also include half-metals such as B, Si, Ge, As, Sb, and Te.
[0515] For example, considering the transparency of the cured film, the average primary particle size is preferably 1 to 200 nm, more preferably 3 to 80 nm.
[0516] The average first-order particle size was calculated by measuring the particle size of any 200 particles using an electron microscope and then arithmetically averaging the results. Additionally, when the particle shape is not spherical, the longest side was used as the particle size.
[0517] When the photosensitive composition layer contains particles, it may contain only one type of metal and different particles of different sizes, or it may contain two or more types.
[0518] The photosensitive composition layer does not contain particles, or when the photosensitive composition layer contains particles, preferably the particle content is more than 0% by mass and less than 35% by mass relative to the total mass of the photosensitive composition layer; more preferably it does not contain particles, or the particle content is more than 0% by mass and less than 10% by mass relative to the total mass of the photosensitive composition layer; even more preferably it does not contain particles, or the particle content is more than 0% by mass and less than 5% by mass relative to the total mass of the photosensitive composition layer; even more preferably it does not contain particles, or the particle content is more than 0% by mass and less than 1% by mass relative to the total mass of the photosensitive composition layer; and most preferably it does not contain particles.
[0519] -Coloring agents-
[0520] The photosensitive composition layer may contain trace amounts of colorants (pigments and dyes, etc.), but preferably does not contain colorants, for example, from the perspective of transparency.
[0521] When the photosensitive composition layer contains a colorant, the content of the colorant relative to the total mass of the photosensitive composition layer is preferably less than 1% by mass, more preferably less than 0.1% by mass. There is no particular limitation on the lower limit, but 0% by mass is preferred.
[0522] -Antioxidants-
[0523] Examples of antioxidants include 3-pyrazolone derivatives such as 1-phenyl-3-pyrazolone (also known as phenidone), 1-phenyl-4,4-dimethyl-3-pyrazolone, and 1-phenyl-4-methyl-4-hydroxymethyl-3-pyrazolone; polyhydroxybenzenes such as hydroquinone, catechol, pyrogallol, methylhydroquinone, and chlorohydroquinone; and p-methylaminophenol, p-aminophenol, p-hydroxyphenylglycine, and p-phenylenediamine.
[0524] In view of the superior effects of the present invention, 3-pyrazolones are preferred as antioxidants, and 1-phenyl-3-pyrazolones are more preferred.
[0525] When the photosensitive composition layer contains an antioxidant, the antioxidant content relative to the total mass of the photosensitive composition layer is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more. There is no particular upper limit, but it is preferably 1% by mass or less relative to the total mass of the photosensitive composition layer.
[0526] [Impurities]
[0527] The photosensitive composition layer may contain impurities.
[0528] Examples of impurities include, for example, sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and their ions.
[0529] Since halide ions, sodium ions, and potassium ions are easily mixed in as impurities, the following contents are preferably set.
[0530] The impurity content in the photosensitive composition layer is preferably 80 ppm or less relative to the total mass of the photosensitive composition layer, more preferably 10 ppm or less, and even more preferably 2 ppm or less. There is no particular limitation on the lower limit, but it is preferably 1 ppb or more relative to the total mass of the photosensitive composition layer, more preferably 0.1 ppm or more.
[0531] As a method for setting impurities within the aforementioned range, examples include: selecting raw materials with low impurity content as raw materials included in the photosensitive composition layer; preventing impurities from being introduced during the formation of the photosensitive composition layer; and cleaning and removing impurities. By using these methods, the amount of impurities can be kept within the aforementioned range.
[0532] For example, impurities can be quantified using known methods such as ICP (Inductively Coupled Plasma) emission spectroscopy, atomic absorption spectroscopy, and ion chromatography.
[0533] The content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and hexane in the photosensitive composition layer is preferably low. The content of these compounds relative to the total mass of the photosensitive composition layer is preferably 100 ppm by mass or less, more preferably 20 ppm by mass or less, and even more preferably 4 ppm by mass or less. There is no particular limitation on the lower limit, but relative to the total mass of the photosensitive composition layer, it is preferably 10 ppb by mass or more, more preferably 100 ppb by mass or more. The content of these compounds can be suppressed using the same method as for the aforementioned metal impurities. Furthermore, they can be quantified using known methods.
[0534] From the perspective of improving reliability and lamination, the water content in the photosensitive composition layer is preferably 0.01 to 1.0% by mass, more preferably 0.05 to 0.5% by mass, relative to the total mass of the photosensitive composition layer.
[0535] [Refractive index adjustment layer]
[0536] The transfer film may have a refractive index adjustment layer disposed on the photosensitive composition layer.
[0537] The transfer film preferably comprises, in sequence, a temporary support, a photosensitive composition layer, and a refractive index adjustment layer.
[0538] In addition, when the transfer film also has a protective film described later, it is preferable to have a temporary support, a photosensitive composition layer, a refractive index adjustment layer and a protective film described later in sequence.
[0539] As a refractive index adjustment layer, known refractive index adjustment layers can be used. Materials included in the refractive index adjustment layer include, for example, adhesives and particles.
[0540] Examples of adhesives include, for instance, adhesive polymers contained in the photosensitive composition layer and polymers having structural units with a carboxylic anhydride structure.
[0541] Examples of particles include, for example, zirconium oxide particles (ZrO2 particles), niobium oxide particles (Nb2O5 particles), titanium oxide particles (TiO2 particles), and silicon dioxide particles (SiO2 particles).
[0542] The refractive index adjustment layer preferably contains a metal oxide inhibitor.
[0543] By including a metal oxidation inhibitor in the refractive index adjustment layer, the oxidation of the metal in contact with the refractive index adjustment layer can be suppressed.
[0544] As metal oxidation inhibitors, compounds having an aromatic ring containing a nitrogen atom within the molecule are preferred, for example. Examples of metal oxidation inhibitors include imidazole, benzimidazole, tetrazolium, mercaptothiadiazole, and benzotriazole.
[0545] The refractive index of the refractive index adjustment layer is preferably 1.60 or higher, more preferably 1.63 or higher. There is no particular upper limit, but it is preferably 2.10 or lower, more preferably 1.85 or lower.
[0546] The thickness of the refractive index adjustment layer is preferably below 500 nm, more preferably below 110 nm, and even more preferably below 100 nm. There is no particular upper limit, but it is preferably above 20 nm, and more preferably above 50 nm.
[0547] The thickness of the refractive index adjustment layer was calculated as the average of five arbitrary points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0548] [Other layers]
[0549] The transfer film may have other layers besides the temporary support, photosensitive composition layer and refractive index adjustment layer mentioned above.
[0550] Other layers include, for example, protective films and antistatic layers.
[0551] The transfer film may have a protective film on the side surface opposite to the temporary support to protect the photosensitive composition layer.
[0552] The protective film is preferably a resin film, and a resin film with heat resistance and solvent resistance can be used.
[0553] Examples of protective films include olefin films such as polypropylene films and polyethylene films. Furthermore, resin films made of the same material as the temporary support described above can also be used as protective films.
[0554] The thickness of the protective film is preferably 1–100 μm, more preferably 5–50 μm, even more preferably 5–40 μm, and particularly preferably 15–30 μm. From the perspective of excellent mechanical strength, the thickness of the protective film is preferably 1 μm or more, and from the perspective of relative cost, it is preferably 100 μm or less.
[0555] The transfer film may include an antistatic layer.
[0556] By having an antistatic layer, the transfer film can suppress the generation of static electricity when peeling off films disposed on the antistatic layer, and can also suppress the generation of static electricity caused by friction with equipment or other films, thus, for example, suppressing the generation of defects in electronic devices.
[0557] The antistatic layer is preferably disposed between the temporary support and the photosensitive composition layer.
[0558] An antistatic layer is a layer with antistatic properties, containing at least an antistatic agent. There are no particular limitations on the antistatic agent; any known antistatic agent can be used.
[0559] [Manufacturing method of transfer film]
[0560] The method for manufacturing the transfer film of the present invention is not particularly limited and can use known methods.
[0561] From the perspective of high productivity, the following method is preferred: coating a photosensitive composition onto a temporary support and drying it as needed to form a photosensitive composition layer.
[0562] The above method will be explained in detail below.
[0563] Examples of coating methods for photosensitive compositions include printing, spraying, roller coating, bar coating, curtain coating, spin coating, and stencil coating (i.e., slot coating).
[0564] Examples of drying methods include natural drying, heat drying, and vacuum drying. These methods can be used individually or in combination.
[0565] In this specification, "drying" means removing at least a portion of the solvent contained in the photosensitive composition.
[0566] When a transfer film has a refractive index adjustment layer on a photosensitive composition layer, for example, the refractive index adjustment layer can be formed by coating a composition for forming a refractive index adjustment layer onto the photosensitive composition layer and then drying it as needed.
[0567] Furthermore, when the transfer film has a protective film, the transfer film can be manufactured by attaching the protective film to the photosensitive composition layer.
[0568] There are no particular limitations on the method of attaching a protective film to the photosensitive composition layer, and well-known methods can be cited.
[0569] As a device for laminating a protective film onto a photosensitive composition layer, known laminators such as vacuum laminators and automatic cutting laminators can be cited.
[0570] The laminator is preferably equipped with any heatable roller, such as a rubber roller, and is capable of applying pressure and heating.
[0571] [Manufacturing method of laminated body]
[0572] By using the above-mentioned transfer film, the photosensitive composition layer can be transferred to the substrate.
[0573] The preferred method for manufacturing the laminate includes:
[0574] In the bonding process, the surface of the transfer film opposite to the temporary support is brought into contact with the object to be transferred to obtain an object with a photosensitive composition layer having the object to be transferred, a photosensitive composition layer and a temporary support in sequence.
[0575] The exposure process involves patterning the photosensitive composition layer; and
[0576] The developing process forms a pattern by developing the exposed photosensitive composition layer;
[0577] The manufacturing method of the laminate also includes:
[0578] The peeling process involves peeling a temporary support from the substrate with the photosensitive composition layer between the bonding process and the exposure process, or between the exposure process and the developing process.
[0579] In the method for manufacturing the laminate of the present invention, this structure enables the suppression of wrinkles when laminating onto a substrate with a step difference, even when using a substrate with a step difference as the transfer body, especially in the region along the step difference. Figure 1 The 44) in the middle can suppress wrinkles when laminated onto a substrate with a step difference.
[0580] The following is a detailed explanation of the sequence of the above-mentioned procedures.
[0581] <Lamination Process>
[0582] The lamination process is a process of laminating the surface of the transfer film opposite to the temporary support to the object to be transferred, thereby obtaining an object with a photosensitive composition layer that sequentially comprises the object to be transferred, a photosensitive composition layer, and a temporary support.
[0583] In addition, when using a substrate with a stepped difference as the transfer object, it is preferable to perform the following process: the photosensitive composition layer on the temporary support of the transfer film is brought into contact with the substrate with a stepped difference and bonded in such a way that the upper part and the lower part of the stepped difference are continuously covered, thereby obtaining a substrate with a photosensitive composition layer having a substrate, a photosensitive composition layer and a temporary support in sequence.
[0584] Furthermore, the surface of the transfer film opposite to the temporary support is preferably a refractive index adjusting layer when the transfer film has a refractive index adjusting layer, and preferably a photosensitive composition layer when the transfer film does not have a refractive index adjusting layer. That is, the lamination process preferably involves contacting the refractive index adjusting layer of the transfer film with the object to be transferred, or contacting the photosensitive composition layer of the transfer film with the object to be transferred.
[0585] The photosensitive composition layer of the transfer film exposed on a temporary support is brought into contact with the substrate to be transferred, thereby bonding them together. Through this bonding, the photosensitive composition layer and the temporary support are disposed on the substrate to be transferred.
[0586] In the above bonding process, the bonding is performed by pressing the surface of the transfer object into contact with the surface of the photosensitive composition layer.
[0587] There are no particular limitations on the above-mentioned lamination method, and known transfer and lamination methods can be used. Preferably, the surface of the photosensitive composition layer is overlapped onto a substrate with a stepped difference, and the process is carried out by pressure and heating based on rollers or the like.
[0588] It can be laminated using well-known laminators such as vacuum laminators and automatic cutting laminators.
[0589] There are no particular restrictions on the type of substrate to be transferred; examples include glass substrates, resin substrates, and metal substrates, as well as laminates of these.
[0590] As a transfer substrate, for example, a substrate with a stepped difference can be cited.
[0591] There are no particular limitations on the preparation method for substrates with stepped differences.
[0592] As a substrate included in a substrate having a stepped difference, a transparent substrate is preferred, for example.
[0593] The substrate with a stepped difference can be pre-treated on the contact surface of the substrate (especially when the substrate is a transparent substrate (front panel)) to improve the adhesion of each layer based on lamination in the above-mentioned bonding process.
[0594] There are no particular limitations on the surface treatment described above, and known methods that can improve the seal can be used.
[0595] Preferably, surface treatment using a silane compound (preferably a silane coupling agent) is implemented. As the silane coupling agent, a silane coupling agent having functional groups that interact with the photosensitive composition layer is preferred. Specifically, a silane coupling agent solution (0.3% by mass aqueous solution of N-β(aminoethyl)γ-aminopropyltrimethoxysilane, trade name: KBM603, manufactured by Shin-Etsu Chemical Co., Ltd.) is sprayed for 20 seconds, rinsed with pure water, and then reacted by heating. A heating bath can be used, or the substrate can be preheated using a laminator.
[0596] When the lower part of the step that constitutes the step difference is a component other than the substrate, the process of setting the other component on the substrate may be included.
[0597] The thickness of the step constituting the aforementioned step difference is preferably 100 nm or more, more preferably 100 to 500 nm, and even more preferably 100 to 300 nm.
[0598] Figure 1 The substrate 43 shown has a stepped difference, with a step 41 forming the stepped difference on substrate 1A. The thickness of the step 41 forming the stepped difference corresponds to the height (distance) between the upper part 41a and the lower part 41b of the step forming the stepped difference. Figure 1 In the text, the thickness of the step 41 constituting the step difference is described as 100 nm, but the substrate with the step difference used in the manufacturing method of the laminate of the present invention is not limited to this type of method.
[0599] Furthermore, in Figure 1 In the text, the size of the step 41 when viewed from above the substrate 1A is described as 2cm in length and 5cm in width, but the above method is only one example and is not limited to this method.
[0600] Furthermore, the upper part of the step that constitutes the step difference can be a plane or a curved surface.
[0601] Furthermore, regarding the shape of the steps that constitute the step difference, the side of the steps that constitute the step difference can be an inclined structure with the upper part of the steps being narrower than the lower part of the steps (the so-called conical shape), or the upper part and the lower part of the steps can be the same structure.
[0602] The stepped side that constitutes the step difference ( Figure 1 41b) and substrate ( Figure 1 The angle formed by 1A) is not particularly limited, but is preferably 5 to 90°.
[0603] Furthermore, the manufacturing method of the laminate of the present invention preferably includes starting from the lower part of the step constituting the aforementioned step difference ( Figure 1 41c) to the upper part of the steps ( Figure 1 41a) The step-gradient rising process of sequentially stacking the aforementioned photosensitive composition layers, and from the upper part of the step constituting the aforementioned step-gradient ( Figure 1 (41a) to the lower part of the steps ( Figure 1 In step 41c), the aforementioned photosensitive composition layers are sequentially stacked in a step-difference decreasing process. Thus, even when including both a step-difference increasing process and a step-difference decreasing process, the method for manufacturing the laminate according to the present invention, particularly in… Figure 1 The region 44 along the step difference can suppress wrinkles from being incorporated during lamination onto a substrate with a step difference. The step difference rising process... Figure 1 The photosensitive composition layer crosses the step in the step difference on the side close to the lamination direction 42. The step difference descent process is performed in... Figure 1 The photosensitive composition layer crosses the step in the step difference on the side away from the lamination direction 42.
[0604] The steps constituting the aforementioned step difference may contain conductive elements. Examples of conductive elements include the conductive layer described later.
[0605] The substrate to be transferred can be a substrate with a conductive layer.
[0606] A substrate with a conductive layer has a conductive layer on the substrate, and any layer can be formed as needed. That is, a substrate with a conductive layer is a conductive substrate that has at least a substrate and a conductive layer disposed on the substrate.
[0607] Examples of substrates include resin substrates, glass substrates, and semiconductor substrates.
[0608] As a preferred substrate, for example, it is described in paragraph
[0140] of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.
[0609] From the perspective of conductivity and fine line formation, the conductive layer is preferably selected from at least one layer selected from metal layers, conductive metal oxide layers, graphene layers, carbon nanotube layers and conductive polymer layers.
[0610] Furthermore, a single conductive layer or two or more conductive layers can be disposed on the substrate. When two or more conductive layers are disposed, conductive layers of different materials are preferred.
[0611] As a preferred embodiment of the conductive layer, for example, it is described in paragraph
[0141] of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.
[0612] As a substrate having a conductive layer, a substrate having at least one of a transparent electrode and a circuitous wiring is preferred. The substrate described above is preferably used as a substrate for a touch panel.
[0613] Transparent electrodes are preferably used as electrodes for touch panels. The transparent electrodes are preferably composed of metal oxide films such as ITO (indium tin oxide) and IZO (indium zinc oxide), as well as fine metal wires such as metal mesh and silver nanowires.
[0614] Examples of fine metal wires include those made of silver and copper. Among these, silver conductive materials such as silver mesh and silver nanowires are preferred.
[0615] Metal is the preferred material for circuitous wiring.
[0616] Metals can be used as materials for circuit routing, including gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, and manganese, as well as alloys composed of two or more of these metallic elements. Among these, copper, molybdenum, aluminum, or titanium are preferred materials for circuit routing, with copper being more preferred.
[0617] <Exposure Process>
[0618] The exposure process is the process of exposing the photosensitive composition layer to a pattern.
[0619] In addition, "pattern exposure" here refers to exposure in a patterned manner, that is, exposure with exposed and unexposed areas.
[0620] There are no particular limitations on the detailed configuration and specific size of the pattern during pattern exposure. In addition, the pattern formed by the development process described later preferably includes fine lines with a width of 20 μm or less, and more preferably includes fine lines with a width of 10 μm or less.
[0621] As the light source for pattern exposure, any light source capable of illuminating at least a wavelength range of the curable photosensitive composition layer (e.g., 365 nm or 405 nm) can be appropriately selected. The dominant wavelength of the exposure light for pattern exposure is preferably 365 nm. Furthermore, the dominant wavelength refers to the wavelength with the highest intensity.
[0622] As light sources, examples include various lasers, light-emitting diodes (LEDs), ultra-high pressure mercury lamps, high pressure mercury lamps, and metal halide lamps.
[0623] The optimal exposure level is 5–200 mJ / cm. 2 More preferably 10–200 mJ / cm 2 .
[0624] Preferred methods for the light source, exposure amount, and exposure method used in the exposure are described, for example, in paragraphs
[0146] to
[0147] of International Publication No. 2018 / 155193, and are incorporated herein by reference.
[0625] <Stripping Process>
[0626] The peeling process is the process of peeling a temporary support from the substrate with the photosensitive composition layer between the bonding process and the exposure process, or between the exposure process and the development process described later.
[0627] There are no particular restrictions on the peeling method, and the same mechanism as the covering film peeling mechanism described in paragraphs
[0161] to
[0162] of Japanese Patent Application Publication No. 2010-072589 can be used.
[0628] <Developing Process>
[0629] The developing process is the process of developing an exposed photosensitive composition layer to form a pattern.
[0630] The development of the above-mentioned photosensitive composition layer can be performed using a developing solution.
[0631] As a developer, an alkaline aqueous solution is preferred. Examples of alkaline compounds that may be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide).
[0632] Examples of development methods include rotary immersion development, spray development, rotational development, and immersion development.
[0633] In this specification, the preferred developer used is, for example, the developer described in paragraph
[0194] of International Publication No. 2015 / 093271.
[0634] As a preferred development method, for example, the development method described in paragraph
[0195] of International Publication No. 2015 / 093271 can be cited.
[0635] There are no particular limitations on the detailed configuration and specific dimensions of the formed pattern, but the pattern should be able to produce the conductive fine lines described later. Furthermore, the spacing between the patterns is preferably 8 μm or less, more preferably 6 μm or less. There are no particular limitations on the lower limit, but spacing of 2 μm or more is common.
[0636] The pattern (protective film of the photosensitive composition layer) formed in the above order is preferably colorless. Specifically, in L * a * b* In the color system, pattern a * The preferred value is -1.0 to 1.0, and the b value of the pattern is... * The preferred value is -1.0 to 1.0.
[0637] <Post-exposure and post-baking processes>
[0638] The manufacturing method of the above-mentioned laminate may include a process of exposing the pattern obtained by the above-mentioned developing process (post-exposure process) and / or a process of heating (post-baking process).
[0639] When both post-exposure and post-baking processes are involved, post-baking is preferably performed after post-exposure.
[0640] [Methods for manufacturing circuit wiring]
[0641] Transfer film can also be used in the manufacturing of circuit wiring.
[0642] There are no particular restrictions on the manufacturing method of circuit wiring, and well-known manufacturing methods can be cited.
[0643] Among them, the preferred method for manufacturing the laminate as a method for manufacturing circuit wiring includes:
[0644] The bonding process involves bonding a photosensitive composition layer on a temporary support of a transfer film to a transfer substrate containing a conductive layer to obtain a transfer substrate having a transfer substrate, a photosensitive composition layer, and a temporary support in sequence.
[0645] The exposure process involves patterning the photosensitive composition layer.
[0646] The developing process forms a pattern by developing the exposed photosensitive composition layer; and
[0647] The etching process involves etching the conductive layer in areas where no pattern is present.
[0648] The manufacturing methods for circuit wiring also include:
[0649] The peeling process involves peeling a temporary support from the substrate with the photosensitive composition layer between the bonding process and the exposure process, or between the exposure process and the developing process.
[0650] In the manufacturing method of circuit wiring, the bonding process, exposure process, development process and stripping process have the same meaning as the processes in the above-mentioned <Manufacturing Method of Laminated Body>, and the preferred range is also the same.
[0651] <Etching Process>
[0652] The etching process is a process of etching the conductive layer in areas where the pattern obtained in the development process is not configured.
[0653] That is, in the etching process, the pattern formed by the photosensitive composition layer is used as a resist to etch the conductive layer.
[0654] As an etching process, known methods can be applied, such as the methods described in paragraphs
[0209] to
[0210] of Japanese Patent Application Publication No. 2017-120435, the methods described in paragraphs
[0048] to
[0054] of Japanese Patent Application Publication No. 2010-152155, wet etching methods immersed in etching solutions, and dry etching methods based on plasma etching.
[0655] The etching solution used in wet etching can be selected appropriately, either acidic or alkaline, depending on the object being etched.
[0656] Examples of acidic etching solutions include, for instance, aqueous solutions of a single acidic component selected from hydrochloric acid, sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, oxalic acid, and phosphoric acid, as well as aqueous solutions of the acidic component mixed with a salt selected from ferric chloride, ammonium fluoride, and potassium permanganate. The acidic component can be a combination of multiple acidic components.
[0657] Examples of alkaline etching solutions include, for instance, aqueous solutions of the alkaline component alone selected from sodium hydroxide, potassium hydroxide, ammonia, organic amines, and salts of organic amines (such as tetramethylammonium hydroxide), as well as aqueous solutions of the alkaline component mixed with salts (such as potassium permanganate). The alkaline component can be a combination of multiple alkaline components.
[0658] <Removal Process>
[0659] The manufacturing method of circuit wiring may include a process of removing residual patterns (removal process).
[0660] There are no particular restrictions on the removal process; it can be performed before or after each process, but it is preferred to perform it after the etching process.
[0661] There are no particular limitations on the method for removing residual patterns. For example, methods such as removal by chemical treatment can be cited, but methods using a removal solution are preferred.
[0662] As a method of removing the residual pattern using a removal solution, one example is to immerse the transfer object with the residual pattern in a stirring removal solution for 1 to 30 minutes.
[0663] The preferred temperature of the removal liquid is 30–80°C, and more preferably 50–80°C.
[0664] Examples of removal solutions include those that dissolve an inorganic or organic base component in water, dimethyl sulfoxide, N-methylpyrrolidone, or a mixture thereof. Examples of inorganic base components include sodium hydroxide and potassium hydroxide. Examples of organic base components include primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium salt compounds.
[0665] Furthermore, it can be removed using a removal liquid and by known methods such as spraying, scrubbing, or immersion.
[0666] [Other processes]
[0667] The manufacturing method of the laminate and the manufacturing method of the circuit wiring may include any process other than the above-mentioned process (other processes).
[0668] As exposure, development and other processes applicable to the manufacturing method of circuit wiring, examples include the processes described in paragraphs
[0035] to
[0051] of Japanese Patent Application Publication No. 2006-023696.
[0669] <Process for reducing visible light reflectivity>
[0670] The manufacturing method of the laminate and the manufacturing method of the circuit wiring may include the following steps: performing a process to reduce the visible light reflectivity of some or all of the multiple conductive layers of the transfer body.
[0671] As a process to reduce visible light reflectivity, oxidation is an example. When the substrate has a copper-containing conductive layer, copper is oxidized to produce copper oxide, and the conductive layer is blackened, thereby reducing the visible light reflectivity of the conductive layer.
[0672] Regarding the treatment of reducing visible light reflectivity, the descriptions in Japanese Patent Application Publication No. 2014-150118 (paragraphs
[0017] to
[0025] ) and Japanese Patent Application Publication No. 2013-206315 (paragraphs
[0041] to
[0042] ,
[0048] and
[0058] ) are incorporated herein by reference.
[0673] <The process of forming an insulating film, and the process of forming a new conductive layer on the surface of the insulating film>
[0674] The manufacturing method of the circuit wiring also preferably includes a step of forming an insulating film on the surface of the circuit wiring and a step of forming a new conductive layer on the surface of the insulating film.
[0675] Through the above process, a first electrode pattern and an insulating second electrode pattern can be formed.
[0676] There are no particular limitations on the process of forming the insulating film, and known methods for forming permanent films can be cited. Furthermore, an insulating film with a desired pattern can be formed by photolithography using a photosensitive material with insulating properties.
[0677] There are no particular limitations on the process of forming a new conductive layer on an insulating film. For example, a new conductive layer with a desired pattern can be formed by photolithography using a photosensitive composition with conductive properties.
[0678] The method for manufacturing circuit wiring preferably uses a transfer body that includes multiple conductive layers on each of its two surface sides, and forms circuits sequentially or simultaneously on the conductive layers disposed on the two surface sides of the transfer body. With this structure, circuit wiring for a touch panel can be formed such that a first conductive pattern is formed on one surface of the transfer body, and a second conductive pattern is formed on the other surface. Furthermore, it is also preferable to form this type of circuit wiring for a touch panel from both sides of the transfer body by roll-to-roll.
[0679] 〔use〕
[0680] The laminates and circuit wiring manufactured using the methods for manufacturing laminates and circuit wiring can be applied to various devices. Examples of devices equipped with laminates or circuit wiring manufactured using the aforementioned methods include display devices, printed circuit boards, semiconductor packages, and input devices; touch panels are preferred, and capacitive touch panels are more preferred. Furthermore, the aforementioned input devices can be applied to display devices such as organic EL display devices and liquid crystal display devices.
[0681] [Manufacturing methods for electronic devices]
[0682] Transfer films can also be used in the manufacturing process of electronic devices.
[0683] As a method for manufacturing the aforementioned electronic device, the method for manufacturing the electronic device using the aforementioned transfer film is preferred.
[0684] The manufacturing method of the electronic device preferably includes the manufacturing method of the above-mentioned laminate.
[0685] Examples of such electronic devices include input devices, with touch panels being a preferred choice. Furthermore, these input devices can be applied to display devices such as organic light-emitting diode (OLED) displays and liquid crystal displays.
[0686] As a method for manufacturing a touch panel, for example, it is also preferable to include a step of etching the conductive layer in the area where the resin pattern is not disposed in a laminate in which a transfer body (e.g., a substrate, a conductive layer (the conductive layer having the substrate)) and a pattern made using the above-mentioned transfer film are sequentially laminated, and more preferably a method of using a pattern manufactured by a manufacturing method including the above-mentioned bonding step, the above-mentioned exposure step and the above-mentioned development step.
[0687] Regarding the specific methods and order of each step in the manufacturing method of a touch panel, including the process of forming wiring for the touch panel, the preferred method is the same as described in the above-mentioned <Method for Manufacturing Circuit Wiring>.
[0688] Furthermore, the manufacturing method of the touch panel, including the process of forming wiring for the touch panel, may include any other process (other processes) besides those described above.
[0689] As a method for forming wiring for a touch panel, for example, International Publication No. 2016 / 190405 can be cited. Figure 1 The method recorded in the text.
[0690] The above-described method for manufacturing a touch panel allows for the production of a touch panel with at least wiring for the touch panel. The touch panel preferably includes a transparent substrate, electrodes, and an insulating or protective layer.
[0691] As for detection methods in touch panels, known methods such as resistive film detection, electrostatic capacitance detection, ultrasonic detection, electromagnetic induction detection, and optical detection can be cited, with electrostatic capacitance detection being preferred.
[0692] Examples of touch panels include, for example, in-cell type (e.g., the touch panel described in Figures 5 to 8 of Japanese Patent Application Publication No. 2012-517051), on-cell type (e.g., the touch panel described in Figure 19 of Japanese Patent Application Publication No. 2013-168125, and the one described in Japanese Patent Application Publication No. 2012-089102). Figure 1 The touch panel shown in Figure 5), OGS (One Glass Solution) type, TOL (Touch-on-Lens) type (e.g., the touch panel shown in Figure 2 of Japanese Patent Application Publication No. 2013-054727), various out-cell types (e.g., GG, G1·G2, GFF, GF2, GF1 and G1F, etc.) and other structures (e.g., the touch panel shown in Figure 6 of Japanese Patent Application Publication No. 2013-164871).
[0693] As a touch panel, for example, the touch panel described in paragraph
[0229] of Japanese Patent Application Publication No. 2017-120345 can be cited.
[0694] In the manufacturing method of electronic devices using transfer film, it is even more preferable (especially when the transfer film contains a negative photosensitive composition layer) that the manufactured electronic device contains a resin pattern as a cured film.
[0695] These resin-patterned cured films can be used as protective films (permanent films) covering part or all of the electrodes and other components of electronic devices (such as touch panels). By applying the aforementioned resin-patterned cured film as a protective film (permanent film) to electrodes and other components, it is possible to prevent metal corrosion, increased resistance between electrodes and driving circuits, and short circuits. Furthermore, other applications of resin-patterned cured films include, for example, various electrode protective films, planarization films, top coatings, hard coatings, passivation films, spacers, partitions, microlenses, optical filters, and anti-reflective films.
[0696] Example
[0697] The present invention will be specifically described below with examples. The materials, amounts, proportions, processing methods, and processing order shown in the following examples can be appropriately modified without departing from the spirit of this specification. Therefore, the scope of the present invention is not limited to the specific examples shown below. Furthermore, unless otherwise specified, "parts" and "%" are mass measurements.
[0698] In the following examples, the weight-average molecular weight (Mw) is calculated from polystyrene based on gel permeation chromatography (GPC).
[0699] [Temporary support]
[0700] <Synthesis of Polyester 1>
[0701] As shown below, terephthalic acid and ethylene glycol were reacted directly to remove water by distillation. After esterification, polyester 1 (hereinafter also referred to as "PET1"), which served as a temporary support, was synthesized by direct esterification under reduced pressure through a continuous polymerization apparatus (Sb catalyst-based PET).
[0702] (Esterification reaction)
[0703] In the first esterification reactor, a slurry was formed by mixing high-purity terephthalic acid (4.7 tons) and ethylene glycol (1.8 tons) for 90 minutes, and continuously fed into the reactor at a flow rate of 3800 kg / h. Simultaneously, an ethylene glycol solution of antimony trioxide was continuously supplied, allowing the reaction to proceed under conditions of 250°C, stirring, and an average residence time of approximately 4.3 hours. Antimony trioxide was continuously added until the amount of Sb added reached 150 ppm (elemental equivalent).
[0704] The reactants were transferred to a second esterification reactor and reacted under stirring, at a reactor temperature of 250°C, and with an average residence time of 1.2 hours. An ethylene glycol solution of magnesium acetate and an ethylene glycol solution of trimethyl phosphate were continuously added to the second esterification reactor until, by elemental conversion, the amount of Mg (magnesium) added reached 65 ppm by mass and the amount of P (phosphorus) reached 35 ppm by mass.
[0705] (Condensation polymerization)
[0706] The esterification product obtained above is continuously fed into the first polycondensation reactor, where it is stirred, reacted at a temperature of 270°C, and the pressure inside the reactor is 20 torr (2.67 × 10⁻⁶). -3 Polycondensation was carried out under conditions of MPa and an average residence time of approximately 1.8 hours.
[0707] Furthermore, it is transferred to a second polycondensation reaction tank, where it is stirred, the temperature inside the tank is 276°C, and the pressure inside the tank is 5 torr (6.67 × 10⁻⁶). -4 The reaction (polymerization) is carried out under conditions of MPa and a residence time of approximately 1.2 hours.
[0708] Next, it is transferred to the third polycondensation reaction tank, where it is kept at a temperature of 278°C and a pressure of 1.5 torr (2.0 × 10⁻⁶). -4 The reaction was carried out under conditions of MPa and a residence time of 1.5 hours (polymerization) to obtain reactant 1 (polyethylene terephthalate (PET)).
[0709] Next, the obtained reactants were ejected in a single strand into cold water and immediately cut to produce polyester granules <cross-section: major diameter approximately 4 mm, minor diameter approximately 2 mm, length approximately 3 mm> to obtain PET1. The obtained PET1 had an IV (inherent viscosity) of 0.63.
[0710] <Synthesis of Polyester 2>
[0711] A mixture of dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (10 parts by mass) and PET1 (90 parts by mass) was granulated using a compounding extruder in the same manner as the production of PET1, thereby obtaining polyester 2 (hereinafter also referred to as "PET2") containing ultraviolet absorber as a raw material for a temporary support.
[0712] <Manufacturing of Temporary Supports>
[0713] (Temporary support C-1)
[0714] After drying PET1 (90 parts by mass) and PET2 (10 parts by mass) to a moisture content of less than 20 ppm by mass, they were fed into the hopper 1 of a single-shaft compounding extruder 1 with a diameter of 50 mm and melted in the extruder 1 at 300°C (intermediate layer II).
[0715] Furthermore, after PET1 is dried to a moisture content of less than 20 ppm by mass, it is fed into the hopper 2 of a 30 mm diameter single-shaft compounding extruder 2 and melted at 300 °C in the extruder 2 (outer layer I and outer layer III).
[0716] The two polymer melts were each passed through a filtration system consisting of a gear pump and a filter (8μm opening, i.e., 8μm pore size). Then, they were layered through two three-layer confluence blocks, with the polymer extruded from extruder 1 forming the intermediate layer (layer II) and the polymer extruded from extruder 2 forming the outer layers (layers I and III). The resulting product was extruded in sheet form through a 120mm wide die. The extrusion conditions were set to a pressure fluctuation of 1% and a temperature distribution of 2% for the molten resin. Specifically, heating was performed at a temperature where the back pressure was increased by 1% relative to the average pressure inside the extruder barrel, and the piping temperature of the extruder was 2% higher than the average temperature inside the extruder barrel.
[0717] Molten resin extruded from the die is applied to a cooling casting roller set at 25°C, and electrostatically bonded to the roller. The resin temperature during extrusion is 300°C. The resin temperature when bonded to the cooling roller is 277°C. The resin is then peeled off using a peeling roller positioned opposite the cooling casting roller, thus obtaining an unstretched polyester film 1. At this point, the output of each extruder is adjusted so that the thickness ratio of layer I, layer II, and layer III is 10 (layer I): 80 (layer II): 10 (layer III).
[0718] Using a stretching roller with a surface roughness Ra of 0.2 μm, the obtained unstretched polyester film 1 was stretched to 4.2 times its original length along the long side at 110°C. Next, it was further stretched to 4.5 times its original length along the width direction using a tenter frame under hot air at 115°C. Then, it was heat-treated at 215°C for 4 seconds under fixed tension, followed by a 0.1% relaxation treatment along the long side and a 3.2% relaxation treatment along the short side, thereby obtaining a biaxially stretched polyester film 1' with a thickness of 16 μm. The obtained biaxially stretched polyester film 1' was then slit by a slitting machine to obtain a temporary support C-1.
[0719] (Temporary support C-2)
[0720] The thickness of the unstretched polyester film 1 obtained in the above-mentioned "manufacturing of the temporary support" was adjusted to 16 μm, stretched to 4.0 times its original length along the long side and 4.7 times its original length along the short side. Otherwise, a biaxially stretched polyester film 2' with a thickness of 16 μm was obtained by the same method as the temporary support C-1. The biaxially stretched polyester film 2' obtained was then slit by a slitting machine to obtain the temporary support C-2.
[0721] (Temporary support C-3)
[0722] The thickness of the unstretched polyester film 1 obtained in the above-mentioned "manufacturing of the temporary support" was adjusted to 25 μm, stretched to 3.8 times its original length along the long side and 4.8 times its original length along the short side. Otherwise, a biaxially stretched polyester film 3' with a thickness of 25 μm was obtained by the same method as the temporary support C1. The biaxially stretched polyester film 3' obtained was slit by a slitting machine to obtain the temporary support C-3.
[0723] (Temporary support C-4)
[0724] The thickness of the unstretched polyester film 1 obtained in the above-mentioned "manufacturing of temporary support" was adjusted to 16 μm, stretched to 4.1 times its original length along the long side, and stretched to 4.8 times its original length along the short side under hot air at 123°C. Otherwise, a biaxially stretched polyester film 4' with a thickness of 16 μm was obtained by the same method as that used for temporary support C-1. The biaxially stretched polyester film 4' obtained was then slit by a slitting machine to obtain temporary support C-4.
[0725] (Temporary support C-5)
[0726] The thickness of the unstretched polyester film 1 obtained in the above-mentioned "manufacturing of temporary support" was adjusted to 25 μm, stretched to 3.8 times its original thickness along the long side, and stretched to 4.8 times its original thickness along the short side under hot air at 110°C. The relaxation treatment in the short side direction was set to 2.4%. Otherwise, a biaxially stretched polyester film 5' with a thickness of 25 μm was obtained by manufacturing in the same way as the temporary support C-1. The biaxially stretched polyester film 5' obtained was slit by a slitting machine to obtain the temporary support C-5.
[0727] [Adhesive Polymer]
[0728] Synthesis of Adhesive Polymer P-1
[0729] A solution was prepared by adding propylene glycol monomethyl ether (82.4 g, FUJIFILM Wako Pure Chemical Corporation) to a flask. The obtained solution was heated to 90°C under a nitrogen atmosphere. Simultaneously, over 3 hours, a solution was added dropwise containing styrene (38.4 g, FUJIFILM Wako Pure Chemical Corporation), dicyclopentyl methacrylate (30.1 g, FANCRYL FA-513M, Hitachi Chemical Co., Ltd.), and methacrylic acid (34.0 g, FUJIFILM Wako Pure Chemical Corporation) dissolved in propylene glycol monomethyl ether (20 g), and a solution containing polymerization initiator V-601 (5.4 g, FUJIFILM Wako Pure Chemical Corporation) dissolved in propylene glycol monomethyl ether acetate (43.6 g, FUJIFILM Wako Pure Chemical Corporation). After the addition was complete, V-601 (0.75 g) was added to the solution three times, every hour. The solution was then allowed to react for another 3 hours. The resulting solution was then diluted with propylene glycol monomethyl ether acetate (58.4 g) and propylene glycol monomethyl ether (11.7 g). The diluted solution was heated to 100°C under an air stream, and tetraethylammonium bromide (0.53 g, FUJIFILM WakoPure Chemical Corporation) and p-methoxyphenol (0.26 g, FUJIFILM Wako Pure Chemical Corporation) were added to the solution. Glycidyl methacrylate (25.5 g, NOFCORPORATION, BLEMMER GH) was added dropwise to the resulting solution over 20 minutes. The solution was then reacted at 100°C for 7 hours to obtain a solution of the adhesive polymer P-1. The solids concentration of the obtained solution was 36.5% by mass. The obtained adhesive polymer has the structural units shown in Table 1. The weight-average molecular weight (Mw) of the standard polystyrene in the GPC is 17,000, the dispersity is 2.4, and the acid value of the polymer is 94.5 mg KOH / g. In all monomers, the amount of residual monomers, as determined by gas chromatography, is less than 0.1% of the solids content of the adhesive polymer.
[0730] In addition, solid components refer to components other than solvents. Even if the aforementioned components are in liquid form, they are still included in the solid components.
[0731] In Table 1, structural units other than those with (meth)acryloyl groups are represented by abbreviations of the monomers used to form each structural unit.
[0732] Structural units having a (meth)acryloyl group are represented as monomer-monomer addition structures. For example, MAA-GMA refers to a structural unit formed by the addition of glycidyl methacrylate to a structural unit derived from methacrylic acid.
[0733] St: Styrene
[0734] MAA-GMA: A structural unit formed by adding glycidyl methacrylate to a structural unit derived from methacrylic acid.
[0735] MAA: Methacrylic acid
[0736] MMA: Methyl methacrylate
[0737] FA: Ethyl acrylate
[0738] BzMA: Benzyl methacrylate
[0739] DCPMA: Dicyclopentyl methacrylate
[0740] [Table 1]
[0741]
[0742] <Synthesis of Adhesive Polymers P-2 to P-4>
[0743] Except for changes in the type and amount of monomers and the amount of initiator, the synthesis was performed using the same method as P-1. The resulting solution had a solids content of 36.3% by mass. The obtained binder polymer has the structural units shown in Table 1. For all monomers, the residual monomer content, as determined by gas chromatography, was less than 0.1% by mass relative to the solids content of the binder polymer.
[0744] Synthesis of Adhesive Polymer P'-1
[0745] Propylene glycol monomethyl ether (270.0 g) was added to a three-necked flask, and the mixture was heated to 70°C under a nitrogen atmosphere while stirring. Meanwhile, allyl methacrylate (45.6 g, FUJIFILM Wako Pure Chemical Corporation) and methacrylic acid (14.4 g) were dissolved in propylene glycol monomethyl ether (270.0 g), and V-65 (3.94 g, FUJIFILM Wako Pure Chemical Corporation) was further dissolved to prepare a dropping solution. This dropping solution was added dropwise to the three-necked flask over 2.5 hours. The resulting solution was stirred and allowed to react for 2 hours. Afterward, the solution was allowed to cool naturally to room temperature, and while stirring ion-exchanged water (2.7 L), the resulting solution was added dropwise to the ion-exchanged water to induce redeposition and obtain a suspension. The suspension was filtered by adding it to a Buchner funnel lined with filter paper, and the filtrate was further washed with ion-exchanged water to obtain a wetted binder polymer P'-1 powder. Next, the mixture was dried under forced air at 45°C to ensure constant yield, and the binder polymer P'-1 was obtained as a powder with a yield of 70%. The structural formula of binder polymer P'-1 is shown below. Furthermore, the percentages of the structural units contained in the binder polymer described below are by mass%.
[0746] [Chemical Formula 25]
[0747]
[0748] [Terminated isocyanate compound Q-1]
[0749] Under a nitrogen atmosphere, butanone oxime (453 g, manufactured by Idemitsu Kosan Co., Ltd.) was dissolved in methyl ethyl ketone (700 g), thus obtaining a solution. Under ice-cold conditions, 1,3-bis(methyl isocyanate)cyclohexane (500 g, a mixture of cis and trans isomers, manufactured by Mitsui Chemicals, Inc., Takenate 600) was added dropwise to the obtained solution over 1 hour, followed by further reaction for another hour. The resulting solution was then heated to 40°C and allowed to react for another hour. 1 The reaction was confirmed to be complete by 1H-NMR (nuclear magnetic resonance) and HPLC (high-speed liquid chromatography), and a methyl ethyl ketone solution of the end-capped isocyanate compound Q-1 represented by the following structural formula was obtained.
[0750] [Chemical Formula 26]
[0751]
[0752] [Preparation of photosensitive composition]
[0753] In each embodiment or comparative example, photosensitive compositions, namely materials A-1 to A-5, with the compositions shown in Table 2 below were prepared. In Table 2, the values of each component represent the content (parts by mass) of each component, and the amount of the adhesive polymer represents the amount of the adhesive polymer solution (solid component concentration 36.3% by mass).
[0754] [Table 2]
[0755]
[0756] [Preparation of the composition for forming the refractive index adjustment layer]
[0757] Next, a composition for forming a refractive index adjustment layer, namely material B-1, was prepared with the composition described in Table 3 below.
[0758] [Table 3]
[0759]
[0760] [Example 1]
[0761] Using a slit nozzle, a photosensitive composition A-1 with a dried thickness of 5.5 μm was coated onto the temporary support C-1 prepared above. The solvent was evaporated in a drying zone at 100°C, thereby forming a photosensitive composition layer 1. Furthermore, using a slit nozzle, a refractive index adjustment layer forming composition B-1 with a dried thickness of 70 nm was coated onto the photosensitive composition layer 1, and dried at a drying temperature of 80°C, thereby forming a refractive index adjustment layer 1. A 25 μm thick polypropylene film (TORAYFAN 25A-KW37, manufactured by TORAYINDUSTRIES, INC.) was pressed onto the refractive index adjustment layer as a protective film to produce the transfer film 1 of Example 1.
[0762] [Examples 2-4 and Comparative Examples 1-3]
[0763] According to Table 4, the components, materials and thicknesses were changed, and the transfer films 2-4 and 1'-3' of Examples 2-4 and Comparative Examples 1-3 were prepared in the same order as in Example 1.
[0764] [Examples 5-8]
[0765] In forming the photosensitive composition layer, according to Tables 2 and 4, each component, each material, and each thickness were changed, and a refractive index adjustment layer was not formed. Otherwise, transfer films 5 to 8 were made in the same order as in Example 1.
[0766] <Fabrication of Layered Structures>
[0767] refer to Figure 1 The manufacturing method of the laminated body is explained.
[0768] A substrate (substrate 43 with stepped difference) was prepared, which has a thickness of 100 nm on a substrate (a COP film with a film thickness of 50 μm and an ITO transparent electrode pattern) and has a copper conductive part that is rectangular in shape with a length of 2 cm and a width of 5 cm when viewed from above the substrate when the lamination direction 42 is set to the vertical direction.
[0769] from Figure 1 The lamination direction 42 shown is used to continuously laminate the surface (refractive index adjustment layer) of the photosensitive composition side exposed by peeling off the protective film of each transfer film in the examples and comparative examples in a manner that covers the entire step difference of the obtained substrate with step difference. This is done under the conditions of rubber roller temperature of 100°C, linear pressure of 100 N / cm and conveying speed of 4.0 m / min, thereby obtaining a laminate with a photosensitive composition layer.
[0770] In addition, the lamination method includes a step-above process in which photosensitive composition layers are sequentially laminated from the lower part of the step to the upper part of the step, and a step-lower process in which photosensitive composition layers are sequentially laminated from the upper part of the step to the lower part of the step.
[0771] 〔evaluate〕
[0772] <Determination of Storage Modulus>
[0773] The long and short sides of the temporary supports C-1 to C-5 fabricated above were used as the long sides, and cut out samples with dimensions of 5mm × 30mm. After conditioning the cut samples at 25℃ and 60% RH (relative humidity) for more than 2 hours, the samples were measured using a dynamic viscoelasticity measuring device (Vibron: DVA-225 (manufactured by IT Measurement & Control Co., Ltd.) along the long side, under conditions of 20mm clamp spacing, a heating rate of 2℃ / min, a measurement temperature range of 30℃ to 150℃, and a frequency of 1Hz. The storage modulus (E) at 80℃ or 100℃ was determined. a1 E a2 E b1 and E b2 ).
[0774] <Evaluation of wrinkles generated during lamination>
[0775] Wrinkles and micro-wrinkles generated in at least one of the refractive index adjustment layer, photosensitive composition layer, and temporary support of the laminate obtained in the above-mentioned <fabricated laminate> were evaluated according to the following criteria.
[0776] In the following evaluation criteria, A or B is preferred. Furthermore, a wrinkle is a wrinkle of a size that can be visually observed, while a micro-wrinkle refers to a wrinkle of a size that, although not visually observable, can be observed under an optical microscope at 20x magnification.
[0777] (Evaluation Criteria)
[0778] A: Within a continuous 200m range of the laminate, no wrinkles were confirmed by visual observation. Furthermore, observation over a 200mm area using a 20x optical microscope... 2 When examining the layered structure, no fine wrinkles were identified.
[0779] B: Within a continuous 200m range of the laminate, no wrinkles were confirmed by visual observation. Furthermore, observation over a 200mm area using a 20x optical microscope... 2 When the number of layers is large, the observed fine wrinkles are more than one and less than ten.
[0780] C: Within a continuous 200m range of the laminate, no wrinkles were confirmed by visual observation. Furthermore, observation over a 200mm area using a 20x optical microscope... 2 When the layered structure is within a certain range, more than 11 fine folds are observed.
[0781] D: Within a continuous 200m range of the laminated body, folds were confirmed to exist on the laminated body through visual observation.
[0782] The evaluation results are shown in Table 4.
[0783] The records in the table represent the following information.
[0784] “E a1 The column indicates the storage modulus E of the temporary support at 100°C along its shorter side. a1 .
[0785] “E a2 The column indicates the storage modulus E of the temporary support at 100°C along its long side. a2 .
[0786] “E b1 The column indicates the storage modulus E of the temporary support at 80°C along its shorter side. b1 .
[0787] “E b2 The column indicates the storage modulus E of the temporary support at 80°C along its long side. b2 .
[0788] “E a1 / E a2The column indicates the storage modulus E of the temporary support at 100°C along its shorter side. a1 Storage modulus E at 100°C relative to the long side of the temporary support a2 The ratio.
[0789] “E b1 / E b2 The column indicates the storage modulus E of the temporary support at 80°C along its shorter side. b1 Storage modulus E at 80°C relative to the long side of the temporary support b2 The ratio.
[0790] The “X” column represents the value obtained by the following formula (1).
[0791] X = {〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 Formula (1) is calculated as follows:}×100
[0792] The column "Geometric Mean at 100℃" represents E a1 With E a2 The square root of the product (geometric mean at 100°C) = √(E a1 ×E a2 )).
[0793] [Table 4]
[0794]
[0795] As shown in Table 4 above, it is confirmed that the desired effect can be obtained when using the transfer film of the present invention.
[0796] Based on the comparison of Examples 1 to 4, the storage modulus E of the temporary support at 100°C in the short side direction was confirmed. a1 Storage modulus E at 100°C relative to the long side of the temporary support a2 The ratio (E) a1 / E a2 The effect is even better when the value is below 1.30. Furthermore, based on the same comparison, it was confirmed that E... a1 / E a2 When the value is below 1.25, the effect is even better.
[0797] Furthermore, based on the comparison between Examples 1 and 4 and Examples 2 to 3, it was confirmed that when X obtained from the above formula (1) is 7.00% or less, the effect is even better.
[0798] [Example 9]
[0799] The resolution and peelability of wiring patterns obtained when the transfer films of Examples 1 to 8 are used as resists for wiring formation were evaluated using the following methods.
[0800] A PET substrate with a copper layer was fabricated by sputtering a 200 nm thick copper layer onto a 100 μm thick polyethylene terephthalate (PET) film.
[0801] <resolution>
[0802] Any of the transfer films produced in Examples 1 to 8 of the roll-up method were rolled out, and the protective film was peeled off from the transfer film. Next, the transfer film and the copper-layered PET substrate were bonded together such that the surface of the transfer film exposed by peeling off the protective film (the refractive index adjustment layer) opposite to the temporary support side was in contact with the copper layer of the copper-layered PET substrate to obtain a laminate. This bonding process was performed under conditions of a roll temperature of 100°C, a linear pressure of 1.0 MPa, and a linear speed of 4.0 m / min.
[0803] From the temporary support side of the obtained laminate, an ultra-high pressure mercury lamp (dominant exposure wavelength: 365 nm) was irradiated through a photomask. The photomask used for exposing the photosensitive composition layer had a duty cycle of 1:1 and a line and space pattern with a line width and a space width of 50 μm. The exposure amount to the photosensitive composition layer was adjusted so that the line width of the resin pattern formed by exposing the area with the line and space pattern (50 μm line width and 50 μm space width) became 50 μm. Then, the temporary support was peeled off from the exposed laminate, and spray development was performed for 30 seconds using a 1.0% by mass sodium carbonate aqueous solution at 25°C. This development process removed the unexposed photosensitive composition layer from the laminate, creating a resin pattern with a line and space pattern on the copper layer surface. When using any of the transfer films in Examples 1-8, a resin pattern with good resolution could be obtained.
[0804] <Peelable>
[0805] Using a copper etching solution (Kanto Chemical Co., INC., Cu-O2), the copper layer in areas without resin patterns was etched within a laminate with a resin pattern on the copper layer surface obtained at the aforementioned <resolution>. The laminates subjected to the above copper etching treatment were then immersed in a stripping solution (Kanto Chemical Co., INC., KP-301) at 40°C, and the stripping solution was stirred at 100 rpm.
[0806] All laminates having resin patterns formed using any one of the transfer films in Examples 1-8 exhibited good peelability; the resin patterns were completely peeled off from the copper layer surface within 2 minutes of the laminate being immersed in the stripping solution. Furthermore, by further washing and drying the obtained laminates, a copper wiring substrate with line and spatial patterns depicted on copper was obtained. When using any one of the transfer films in Examples 1-8, well-resolved copper wiring patterns could be obtained.
[0807] Symbol Explanation
[0808] 1A - Substrate, 41 - Step forming a step difference, 41a - Upper part of the step, 41b - Side part of the step, 41c - Lower part of the step, 42 - Lamination direction, 43 - Substrate with step difference, 44 - Region along the step difference.
Claims
1. A transfer film, which is an elongated transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support. The energy storage modulus E of the temporary support at 100°C along its short side a1 Storage modulus E at 100°C relative to the long side of the temporary support a2 The ratio is below 1.
40. The storage modulus E of the temporary support in the short-side direction at 100°C a1 The energy storage modulus E of the temporary support in the long direction at 100°C a2 The geometric mean is above 1.00 GPa and below 5.00 GPa. The thickness of the photosensitive composition layer is 3.0 μm or more. The X obtained from equation (1) is below 7.00%. X={[(E b1 / E b2 )-(E a1 / E a2 )] / (E b1 / E b2 )}×100 Equation (1) E a1 The storage modulus of the temporary support at 100°C along its short side, in GPa. E a2 The storage modulus of the temporary support at 100°C along its long side, in GPa. E b1 The storage modulus of the temporary support at 80°C along its short side, in GPa. E b2 The energy storage modulus of the temporary support at 80°C along its long side is expressed in GPa.
2. The transfer film according to claim 1, wherein, The thickness of the temporary support is less than 40.0 μm.
3. The transfer film according to claim 1 or 2, wherein, The thickness of the photosensitive composition layer is 3.0 μm or more and 20.0 μm or less.
4. The transfer film according to claim 1 or 2, wherein, The photosensitive composition layer comprises an adhesive polymer, a polymerizable compound, and a polymerization initiator.
5. The transfer film according to claim 1 or 2, further comprising a refractive index adjustment layer disposed on the photosensitive composition layer.
6. The transfer film according to claim 1 or 2, wherein, The photosensitive composition layer is used to form an electrode protective film for a touch panel.
7. The transfer film according to claim 1 or 2, wherein, The temporary support is a temporary support in which the outer layer is stacked on both sides of the middle layer.
8. The transfer film according to claim 1 or 2, wherein the photosensitive composition layer is formed on the temporary support.
9. The transfer film according to claim 1 or 2, wherein, The thickness of the temporary support is less than 30.0 μm.
10. A method for manufacturing a laminate, comprising: In the bonding process, the surface of the transfer film opposite to the temporary support of any one of claims 1 to 9 is bonded to the transfer body to obtain a transfer body having the transfer body, the photosensitive composition layer and the temporary support in sequence; The exposure process involves patterning the photosensitive composition layer. and The developing process involves developing the exposed photosensitive composition layer to form a pattern; The method for manufacturing the laminated body further includes: In the peeling process, between the bonding process and the exposure process or between the exposure process and the developing process, the temporary support is peeled off from the transfer substrate with the photosensitive composition layer.
11. A method for manufacturing circuit wiring, comprising: In the bonding process, the surface of the transfer film opposite to the temporary support of any one of claims 1 to 9 is bonded to the transfer body containing the conductive layer to obtain a transfer body having the transfer body, the photosensitive composition layer and the temporary support in sequence. The exposure process involves patterning the photosensitive composition layer. The developing process involves developing the exposed photosensitive composition layer to form a pattern; and The etching process involves etching the conductive layer in areas where the pattern is not configured. The method for manufacturing the circuit wiring further includes: In the peeling process, between the bonding process and the exposure process or between the exposure process and the developing process, the temporary support is peeled off from the transfer substrate with the photosensitive composition layer.
12. The method for manufacturing a laminate according to claim 10, wherein, The substrate to be transferred is a substrate with a stepped difference.
Citation Information
Patent Citations
JP1973042965B1
Insatsuinki oyobi hifukuzairyonotameno hikarijugokanonaketsugozai
JP1976082102A
Photopolymerizable composition
JP1977134692A
JP1980034414B2
Coating composition and curing method
JP1984138205A